Laminate and reflective display device using same

A multilayer laminate with controlled aluminum oxide and hydroxide distribution enhances barrier properties, addressing the need for improved oxygen and water vapor resistance in electronic paper, ensuring display quality and durability.

JP7619105B2Active Publication Date: 2025-01-22DAI NIPPON PRINTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021042476
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-16
Publication Date
2025-01-22
Estimated Expiration
2041-03-16

AI Technical Summary

Technical Problem

Existing laminated films used in electronic paper require improved oxygen and water vapor barrier properties to prevent deterioration of the display medium layer.

Method used

A multilayer structure is developed with a denser aluminum oxide film formed on aluminum hydroxide, enhancing barrier properties by controlling the distribution of aluminum oxide and aluminum hydroxide, and incorporating an organic coating layer to improve durability and flexibility.

Benefits of technology

The laminate provides high barrier properties against oxygen and water vapor, maintaining the integrity of the display medium layer in electronic paper, thereby improving display quality and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619105000005
    Figure 0007619105000005
  • Figure 0007619105000006
    Figure 0007619105000006
  • Figure 0007619105000007
    Figure 0007619105000007
Patent Text Reader

Abstract

To provide a laminate having high barrier properties and favorably used as an optical member to be used in electronic paper, etc. and a reflection type display device using the same.SOLUTION: Provided is a laminate of an antireflection layer and / or an antiglare layer, and a barrier film having an aluminum oxide vapor deposition film. When etched by a TOF-SIMS from a front side opposite to a substrate of the barrier film, an intensity derived from Al2O3 and an intensity derived from Al2O4H are detected in an area of the aluminum oxide vapor deposition film. A maximum peak of the intensity derived from Al2O4H is present at a depth position of 50% to 99% from a film interface in the aluminum oxide vapor deposition film. An (Al2O4H / Al2O3) intensity ratio detected at a position of the maximum peak is 1.0 or more. An intensity peak derived from Al3 is not detected in the area of the aluminum oxide vapor deposition film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a reflective display device using the same. [Background technology]

[0002] Conventionally, laminated films having a film formed on a substrate such as a long film or sheet of plastic etc. have been used for various purposes. For example, a barrier laminated film has been developed in which a barrier layer made of a thin film of aluminum oxide etc. is provided on a plastic film to provide a barrier function against oxygen and water vapor.

[0003] As a method for producing a barrier film having a thin aluminum oxide film, for example, Patent Document 1 discloses that moisture contained in a reaction space where an oxidation reaction between oxygen gas and evaporated aluminum occurs is removed during deposition, thereby suppressing the generation of aluminum hydroxide and improving hot water resistance.

[0004] On the other hand, one application of the above-mentioned barrier film is electronic paper, which is a reflective display device. Electronic paper can be classified into a passive matrix display in which transparent electrodes and back electrodes are patterned to display as segments, and an active matrix display in which the back electrode is endowed with a TFT switching function to display gradations. In either case, an anti-glare layer or an anti-reflection layer is formed on the surface on the viewing side to improve visibility.

[0005] Since the display quality of electronic paper decreases when the display medium layer comes into contact with gases such as oxygen or moisture such as water vapor and deteriorates, the electronic paper has a structure in which a barrier layer is disposed on the outside of the display medium layer (Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-203427 A [Patent Document 2] JP 2019-060946 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the electronic paper having the above-mentioned configuration, further improvement in oxygen barrier property and water vapor barrier property is required to suppress deterioration of the display medium layer. An object of the present invention is to provide a laminate having high barrier property and being suitably used as an optical member for electronic paper, etc., and a reflective display device using the same. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the inventors have discovered that by focusing on the distribution of aluminum oxide and aluminum hydroxide in an aluminum oxide vapor-deposited film, it is possible to obtain a laminate having even higher barrier properties, and have thus completed the present invention.

[0009] Since aluminum hydroxide has a high affinity for water molecules, water molecules penetrate into the film made of aluminum hydroxide and reduce the barrier property against water vapor. Here, in the method of Patent Document 1, the number of hydroxyl groups (hydrogen atoms) in the entire aluminum oxide film decreases.

[0010] However, according to the findings of the present inventors, the aluminum oxide vapor deposition film grows on the aluminum hydroxide surface in a two-dimensional manner, forming a denser aluminum oxide vapor deposition film. In other words, the aluminum oxide film deposited on the aluminum hydroxide surface has the characteristic of exhibiting superior barrier properties against oxygen and water vapor compared to aluminum oxide deposited directly on the surface of a plastic film.

[0011] Therefore, in order to realize a barrier film with high barrier performance, it is possible to provide even higher barrier properties by forming an alumina hydroxide region in the vicinity of the interface between the plastic film and the aluminum vapor deposition, and then forming an aluminum oxide region mainly on this alumina hydroxide region.

[0012] Specifically, the present invention provides the following:

[0013] (1) A barrier film having at least a substrate, an aluminum oxide vapor deposition film, and an organic coating layer laminated in this order; An antireflection layer and / or an antiglare layer formed on a surface of the substrate opposite to the aluminum oxide vapor-deposited film, When the barrier film was etched from the surface side opposite the substrate by time-of-flight secondary ion mass spectrometry (TOF-SIMS), In the region of the aluminum oxide vapor deposition film, an intensity derived from elemental bond Al2O3 and an intensity derived from elemental bond Al2O4H are detected, the intensity derived from the element bond Al2O4H has a maximum peak, the maximum peak being present at a depth position of 50% to 99% from the film interface on the side opposite to the substrate in the aluminum oxide vapor-deposited film, an intensity ratio (Al2O4H / Al2O3) of the elemental bond Al2O4H to the elemental bond Al2O3 detected at the position of the maximum peak is 1.0 or more; A laminate, in which no intensity peak derived from elemental bond Al3 is detected in the region of the aluminum oxide vapor deposition film.

[0014] (2) A barrier film having at least a substrate, an aluminum oxide vapor deposition film, and an organic coating layer laminated in this order; A laminate comprising a support and an antireflection layer and / or an antiglare layer formed on a surface of the support opposite to the barrier film, When the barrier film was etched from the surface side opposite the substrate by time-of-flight secondary ion mass spectrometry (TOF-SIMS), In the region of the aluminum oxide vapor deposition film, an intensity derived from elemental bond Al2O3 and an intensity derived from elemental bond Al2O4H are detected, the intensity derived from the element bond Al2O4H has a maximum peak, the maximum peak being present at a depth position of 50% to 99% from the film interface on the side opposite to the substrate in the aluminum oxide vapor-deposited film, an intensity ratio (Al2O4H / Al2O3) of the elemental bond Al2O4H to the elemental bond Al2O3 detected at the position of the maximum peak is 1.0 or more; A laminate, in which no intensity peak derived from elemental bond Al3 is detected in the region of the aluminum oxide vapor deposition film.

[0015] (3) The laminate according to (1) or (2), wherein the thickness of the aluminum oxide vapor-deposited film is more than 15 nm and less than 60 nm.

[0016] (4) The laminate according to any one of (1) to (3), wherein the organic coating layer is a cured product of a resin composition containing a metal alkoxide and a hydroxyl group-containing water-soluble resin.

[0017] (5) The laminate according to any one of (1) to (4), wherein the barrier film comprises at least a substrate, a first aluminum oxide vapor-deposited film, a first organic coating layer, a second aluminum oxide vapor-deposited film, and a second organic coating layer laminated in this order.

[0018] (6) A reflective display device comprising: two opposing electrodes, at least one of which is a transparent electrode; and a display medium layer disposed between the electrodes and including a display medium, A laminate according to any one of (1) to (5) is provided on the transparent electrode side, A reflective display device, wherein the anti-reflection layer and / or the anti-glare layer is disposed on the outer side.

[0019] (7) A front panel is formed by the laminate according to any one of (1) to (5) and the transparent electrode, The reflective display device according to (6), wherein the front panel, the display medium layer, and a rear panel including a rear electrode are laminated in this order. Effect of the Invention

[0020] According to the present invention, it is possible to provide a laminate having high barrier properties and suitable for use as an optical member for use in, for example, electronic paper, and a reflective display device using the same. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a first laminate according to one embodiment of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view showing another example of the first laminate according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a second laminate according to one embodiment of the present invention. [Figure 4] 1 is a diagram showing an example of a film forming apparatus according to an embodiment of the present invention; [Diagram 5] FIG. 2 is a cross-sectional view showing an example of a plasma pretreatment mechanism of a film forming apparatus. [Figure 6] 2 is a plan view showing an example of an electrode unit and a magnetic field generating unit of a plasma pretreatment mechanism of a film forming apparatus. FIG. [Figure 7] 2 is a cross-sectional view showing an example of an electrode unit and a magnetic field generating unit of a plasma pretreatment mechanism of a film forming apparatus. FIG. [Figure 8] FIG. 2 is a cross-sectional view showing an example of a film forming mechanism of a film forming apparatus. [Figure 9] 1 is a cross-sectional view showing an example of a reflective display device according to an embodiment of the present invention. [Figure 10] FIG. 11 is a cross-sectional view showing another example of a reflective display device according to an embodiment of the present invention. [Figure 11] FIG. 11 is a cross-sectional view showing still another example of a reflective display device according to an embodiment of the present invention. [Figure 12] FIG. 1 is a graph analysis diagram showing the measurement results of the barrier film of Comparative Example 1 by TOF-SIMS. [Figure 13]FIG. 2 is a graph analysis diagram showing the measurement results of the barrier film of Example 1 by TOF-SIMS. [Figure 14] FIG. 13 is a graph analysis diagram showing the measurement results of the barrier film of Comparative Example 2 by TOF-SIMS. [Figure 15] FIG. 13 is a graph analysis diagram showing the measurement results of the barrier film of Comparative Example 3 by TOF-SIMS. [Figure 16] FIG. 13 is a graph analysis diagram showing the measurement results of the barrier film of Comparative Example 4 by TOF-SIMS. [Figure 17] FIG. 2 is a plan view showing an example of a loop stiffness measuring device. [Figure 18] FIG. 18 is a cross-sectional view of the loop stiffness measuring device of FIG. 17 taken along line VV. [Figure 19] FIG. 1 is a diagram for explaining a process of attaching a test piece to a loop stiffness measuring device. [Figure 20] FIG. 13 is a diagram for explaining a step of forming a loop portion in a test piece. [Figure 21] FIG. 13 is a diagram for explaining a process of applying a load to a loop portion of a test piece. [Figure 22] FIG. 13 is a diagram for explaining a process of applying a load to a loop portion of a test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as appropriate within the scope of the object of the present invention. In addition, in this specification, the expression "X to Y" (X and Y are arbitrary numbers) means "X or more and Y or less."

[0023] <First laminate> 1 is a cross-sectional view showing a first laminate 100A as an example of the laminate of the present invention. In this embodiment, an antireflection layer and / or an antiglare layer 160 is formed on the surface of a substrate 120 opposite to the aluminum oxide vapor-deposited film.

[0024] Specifically, the first laminate 100A in Fig. 1 includes a substrate 120, an aluminum oxide deposition film 130b and an organic coating layer 130a formed on one surface of the substrate 120 to form a barrier film, and further includes an anti-reflection layer and / or anti-glare layer 160 formed on the other surface of the first substrate 120. The organic coating layer 130a forms an overcoat layer, and is located on the surface of the laminate 100A. In the laminate 100A, the aluminum oxide deposition film 130b and the organic coating layer 130a form a two-layer structure to form the barrier layer 130. The organic coating layer 130a may be a primer layer, which will be described later.

[0025] FIG. 2 is a cross-sectional view showing another example of the first laminate. The first laminate 100B includes a base material 120, a first aluminum oxide deposition film 130b and a first organic coating layer 130a formed on one side of the base material 120, and a second aluminum oxide deposition film 131b and a second organic coating layer 131a, which constitute a barrier film, and further includes an anti-reflection layer and / or an anti-glare layer 160 formed on the other side of the first base material 120. The organic coating layer 131a constitutes an overcoat layer, and the organic coating layer 131a is located on the surface of the first laminate 100B. In the first laminate 100B, a barrier layer 135 is constituted of four layers of aluminum oxide deposition film / organic coating layer / aluminum oxide deposition film / organic coating layer. The organic coating layer 130a and the organic coating layer 131a may be primer layers, which will be described later.

[0026] In this specification, "laminated in this order" means that the base material, the aluminum oxide vapor-deposited film, and the organic coating layer are laminated in this order, and another layer such as a vapor-deposited primer layer may be laminated as an undercoat between these layers, for example, between the base material and the aluminum oxide vapor-deposited film.

[0027] In addition, "an anti-reflection layer and / or an anti-glare layer formed on the surface opposite to the aluminum oxide vapor-deposited film of the substrate" includes not only the case where an anti-reflection layer and / or an anti-glare layer is formed directly on the surface, but also the case where an anti-reflection layer and / or an anti-glare layer is formed via a primer layer.

[0028] <Second laminate> 3 is a cross-sectional view showing a second laminate 100C. In this embodiment, a support 150 and an antireflection layer and / or an antiglare layer 160 are formed on the surface of the support 150 opposite to the barrier film.

[0029] Specifically, the second laminate 100C in Fig. 3(a) constitutes a barrier film by a substrate 120, an aluminum oxide deposition film 130b formed on one surface of the substrate 120, and an organic coating layer 130a. An antireflection layer and / or antiglare layer 160 is formed on one surface of a support 150, and is laminated on the other surface of the substrate 120 via a pressure-sensitive adhesive layer or adhesive layer 140 (hereinafter referred to as a tacky adhesive layer 140). That is, in the second laminate 100C, the antireflection layer and / or antiglare layer 160 is disposed on the surface of the substrate layer 120 opposite the barrier layer 130 via the support 150.

[0030] 3(b), a barrier film is formed by a substrate 120, an aluminum oxide deposition film 130b formed on one surface of the substrate 120, and an organic coating layer 130a. An antireflection layer and / or antiglare layer 160 is formed on one surface of a support 150, and is laminated with a barrier layer 130 on the other surface of the support 150 via a pressure-sensitive adhesive layer or adhesive layer 140 (hereinafter referred to as a pressure-sensitive adhesive layer 140). That is, in the second laminate 100D, the antireflection layer and / or antiglare layer 160 is disposed on the barrier layer 130 side of the substrate layer 120 via the support 150.

[0031] In the second stacked bodies 100C and 100D, the barrier layer 130 may be composed of four barrier layers 135 as shown in FIG.

[0032] The term "antireflection layer and / or antiglare layer formed on the surface of the support opposite to the barrier film" includes not only the case where the antireflection layer and / or antiglare layer is formed directly on the surface, but also the case where the antireflection layer and / or antiglare layer is formed via a primer layer.

[0033] Hereinafter, each layer constituting the first laminates 100A and 100B and the second laminates 100C and 100D will be described.

[0034] [Base material] The substrate 120 will be described below, but the same material as the substrate 120 can be used for the support 150 described later, and the two may be the same or different.

[0035] The substrate 120 is a layer mainly containing a resin. The resin is not particularly limited, and a known resin film or sheet can be used. For example, a resin film containing a polyester resin including a polyethylene terephthalate resin, a polybutylene terephthalate resin, a polyethylene naphthalate resin, or the like, a polyamide resin, or a polyolefin resin including a polymer or copolymer of α-olefin such as polyethylene or polypropylene, or the like can be used.

[0036] Among these resins, polyester resins are preferably used, and among polyester resins, polyethylene terephthalate resins and polybutylene terephthalate resins are preferably used. The polyester film used as the substrate 120 may be stretched in a predetermined direction. In this case, the polyester film may be a uniaxially stretched film stretched in one predetermined direction, or a biaxially stretched film stretched in two predetermined directions. For example, when a film made of polyethylene terephthalate is used as the substrate 120, a biaxially stretched polyethylene terephthalate film can be used.

[0037] The thickness of the polyester film used as the substrate 120 as described above is not particularly limited as long as it can be used for pretreatment and film formation when forming the aluminum oxide vapor-deposited films 130b, 131b by a film-forming device described later, but from the viewpoint of flexibility and shape retention, a range of 6 μm to 100 μm is preferable. If the thickness of the polyester film is within the above range, it is easy to bend and does not break during transportation, and is easy to handle in a film-forming device used to manufacture a barrier film having the aluminum oxide vapor-deposited films 130b, 131b with improved adhesion.

[0038] As the polyethylene terephthalate film (PET film), in addition to conventionally known PET films, a biomass PET film, a recycled PET film, or a high stiffness PET film (tough PET film) may be used as the substrate 120.

[0039] <Biomass PET film> Biomass PET film is a resin film containing biomass-derived polyester, in which the diol unit is ethylene glycol derived from biomass and the dicarboxylic acid unit is dicarboxylic acid derived from fossil fuels.

[0040] Since biomass-derived ethylene glycol has the same chemical structure as conventional fossil fuel-derived ethylene glycol, a polyester film synthesized using biomass-derived ethylene glycol is comparable to conventional fossil fuel-derived polyester films in terms of physical properties such as mechanical properties. Therefore, a substrate using a biomass-derived polyester film has a layer made of a carbon-neutral material, and therefore can reduce the amount of fossil fuel used and the environmental load compared to substrates manufactured from raw materials obtained from conventional fossil fuels.

[0041] Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass such as sugarcane and corn. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.

[0042] The dicarboxylic acid unit of the polyester uses a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid, an aromatic dicarboxylic acid, an aliphatic dicarboxylic acid, and a derivative thereof can be used. As the aromatic dicarboxylic acid, terephthalic acid and isophthalic acid can be mentioned, and as the derivative of the aromatic dicarboxylic acid, a lower alkyl ester of the aromatic dicarboxylic acid, specifically, methyl ester, ethyl ester, propyl ester, butyl ester, etc. can be mentioned. Among these, terephthalic acid is preferable, and as the derivative of the aromatic dicarboxylic acid, dimethyl terephthalate is preferable.

[0043] The biomass-derived polyester can be obtained by a conventionally known method of polycondensing a diol unit and a dicarboxylic acid unit. Specifically, the polyester can be produced by a general melt polymerization method in which an esterification reaction and / or an ester exchange reaction between the dicarboxylic acid component and the diol component is followed by a polycondensation reaction under reduced pressure, or by a known solution heating dehydration condensation method using an organic solvent.

[0044] The resin composition constituting the resin film containing biomass-derived polyester may be composed of only biomass-derived polyester, or may contain fossil fuel-derived polyester in addition to biomass-derived polyester. Fossil fuel-derived polyester is composed of diol units and dicarboxylic acid units, and is obtained by polycondensation reaction using ethylene glycol, a diol derived from fossil fuel, as the diol unit and dicarboxylic acid derived from fossil fuel as the dicarboxylic acid unit.

[0045] The resin in the resin composition constituting the resin film containing the biomass-derived polyester may contain recycled polyester in addition to the biomass-derived polyester. The recycled polyester may be a recycled polyester derived from biomass or a recycled polyester derived from fossil fuels.

[0046] The resin composition constituting the resin film containing the biomass-derived polyester may contain various additives. Examples of additives include plasticizers, UV stabilizers, coloring inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, release agents, antioxidants, ion exchange agents, and color pigments. The additives are preferably contained in the entire resin composition containing PET in an amount of 5% by mass to 50% by mass, and more preferably 5% by mass to 20% by mass.

[0047] The resin film containing the biomass-derived polyester can be formed, for example, by forming it into a film by the T-die method. Specifically, after drying the above-mentioned PET, the resin composition is fed to a melt extruder heated to a temperature (Tm) to Tm+70°C above the melting point of PET to melt the resin composition, and extruded into a sheet shape from a die such as a T-die, and the extruded sheet-like material is quenched and solidified by a rotating cooling drum, etc., to form a film. As the melt extruder, a single-screw extruder, a twin-screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose. Hereinafter, the melting point may be expressed as Tm, and the glass transition point as Tg, as necessary.

[0048] Carbon dioxide in the atmosphere contains a certain percentage of 14C (105.5 pMC), so it is known that the 14C content in plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain almost no 14C. Therefore, the percentage of carbon derived from biomass can be calculated by measuring the percentage of 14C contained in the total carbon atoms in polyester. In the present invention, the "biomass ratio" indicates the mass ratio of biomass-derived components. Taking PET (polyethylene terephthalate) as an example, PET is a polymer of ethylene glycol containing 2 carbon atoms and terephthalic acid containing 8 carbon atoms in a molar ratio of 1:1. When only biomass-derived ethylene glycol is used, the mass ratio of biomass-derived components in PET is 31.25%, so the biomass ratio is 31.25% (molecular weight derived from biomass-derived ethylene glycol / molecular weight of one unit of polyester polymerization=60÷192). In addition, the mass ratio of the biomass-derived component in the fossil fuel-derived polyester is 0%, and the biomass degree of the fossil fuel-derived polyester is 0%. In the present invention, the biomass degree in the resin film containing the biomass-derived polyester is preferably 5.0% or more, more preferably 10.0% or more, and preferably 30.0% or less.

[0049] The resin film containing the biomass-derived polyester is preferably biaxially stretched. The biaxial stretching can be performed by a conventionally known method. For example, the film extruded onto the cooling drum as described above is subsequently heated by roll heating, infrared heating, or the like, and stretched in the longitudinal direction to obtain a longitudinally stretched film. This stretching is preferably performed by utilizing the peripheral speed difference between two or more rolls. The longitudinal stretching is usually performed in a temperature range of 50 to 100°C. In addition, the longitudinal stretching ratio is preferably 2.5 times or more and 4.2 times or less, depending on the required properties of the film application. If the stretching ratio is less than 2.5 times, the thickness unevenness of the polyester film becomes large, making it difficult to obtain a good film.

[0050] The longitudinally stretched film is then subjected to the sequential processes of transverse stretching, heat setting, and heat relaxation to become a biaxially stretched film. Transverse stretching is usually performed at a temperature range of 50 to 100°C. The transverse stretching ratio is preferably 2.5 times or more and 5.0 times or less, depending on the required properties of the application. If it is less than 2.5 times, the thickness of the film becomes uneven and it is difficult to obtain a good film, and if it exceeds 5.0 times, breakage is likely to occur during film formation.

[0051] After the transverse stretching, a heat setting treatment is subsequently performed, and the preferred temperature range for heat setting is Tg+70 to Tm-10° C. of the polyester. The heat setting time is preferably 1 to 60 seconds. For applications requiring a reduction in the heat shrinkage rate, a heat relaxation treatment may be performed as necessary.

[0052] The thickness of the resin film containing biomass-derived polyester is optional depending on the application, but is usually about 5 to 500 μm. The breaking strength of the resin film containing biomass-derived polyester is 5 to 40 kgf / mm in the MD direction. 2 , 5~35kgf / mm in TD direction 2 The elongation at break is 50 to 350% in the MD direction and 50 to 300% in the TD direction. The shrinkage rate when left in a 150°C environment for 30 minutes is 0.1 to 5%.

[0053] Resin films containing biomass-derived polyesters can be suitably used for packaging products such as bags, lids, and laminated tubes, various label materials, sheet molded products, etc. When using a resin film containing recycled PET for packaging products, the thickness of the stretched film is preferably 5 to 30 μm.

[0054] <Recycled PET film> The recycled PET film is a resin film containing recycled PET, and includes PET recycled by mechanical recycling. Specifically, it includes PET recycled by mechanical recycling of PET bottles, and this PET contains ethylene glycol as a diol component and terephthalic acid and isophthalic acid as dicarboxylic acid components.

[0055] Mechanical recycling is a method in which collected polyethylene terephthalate resin products such as PET bottles are generally crushed, washed with an alkali to remove dirt and foreign matter from the surface of the PET resin products, and then dried at high temperature and reduced pressure for a certain period of time to diffuse and decontaminate the contaminants remaining inside the PET resin, thereby removing dirt from the resin products made of PET resin and returning them to PET resin.

[0056] Hereinafter, polyethylene terephthalate made from recycled PET bottles will be referred to as "recycled polyethylene terephthalate (hereinafter also referred to as recycled PET)," and polyethylene terephthalate that has not been recycled will be referred to as "virgin polyethylene terephthalate (hereinafter also referred to as virgin PET)."

[0057] The content of isophthalic acid in the PET substrate is preferably 0.5 mol% to 5 mol%, more preferably 1.0 mol% to 2.5 mol%, based on the total dicarboxylic acid components constituting the PET. If the content of isophthalic acid is less than 0.5 mol%, flexibility may not be improved, whereas if it exceeds 5 mol%, the melting point of the PET may decrease, resulting in insufficient heat resistance.

[0058] In addition to ordinary PET derived from fossil fuels, the PET may be PET derived from biomass, which is a PET that uses ethylene glycol derived from biomass as a diol component and dicarboxylic acid derived from fossil fuels as a dicarboxylic acid component.

[0059] The PET used in the PET bottle can be obtained by a conventionally known method of polycondensing the above-mentioned diol component and dicarboxylic acid component. Specifically, it can be produced by a general melt polymerization method in which the above-mentioned diol component and dicarboxylic acid component are subjected to an esterification reaction and / or transesterification reaction, followed by a polycondensation reaction under reduced pressure, or a known solution heating dehydration condensation method using an organic solvent. The amount of the diol component used in producing the above-mentioned PET is substantially equimolar to 100 moles of dicarboxylic acid or its derivative, but is generally used in an excess of 0.1 mol% to 20 mol% because of distillation during the esterification and / or transesterification reaction and / or polycondensation reaction. In addition, the polycondensation reaction is preferably carried out in the presence of a polymerization catalyst. The timing of adding the polymerization catalyst is not particularly limited as long as it is before the polycondensation reaction, and it may be added when the raw materials are charged, or it may be added when the pressure reduction starts.

[0060] After the PET recycled from PET bottles is polymerized and solidified as described above, it may be subjected to solid-state polymerization as necessary to further increase the degree of polymerization or to remove oligomers such as cyclic trimers. Specifically, the solid-state polymerization is carried out by cutting the PET into chips, drying the chips, heating the chips at a temperature of 100° C. to 180° C. for about 1 to 8 hours to pre-crystallize the PET, and then heating the chips at a temperature of 190° C. to 230° C. for 1 to several tens of hours in an inert gas atmosphere or under reduced pressure.

[0061] The intrinsic viscosity of the PET contained in the recycled PET is preferably 0.58 dl / g or more and 0.80 dl / g or less. If the intrinsic viscosity is less than 0.58 dl / g, the mechanical properties required for the PET film as a resin substrate may be insufficient. On the other hand, if the intrinsic viscosity exceeds 0.80 dl / g, the productivity in the film forming process may be impaired. The intrinsic viscosity is measured in an orthochlorophenol solution at 35°C.

[0062] The recycled PET preferably contains recycled PET at a ratio of 50% by mass to 95% by mass, and may contain virgin PET in addition to recycled PET. Virgin PET may be PET in which the diol component is ethylene glycol and the dicarboxylic acid component contains terephthalic acid and isophthalic acid as described above, or PET in which the dicarboxylic acid component does not contain isophthalic acid. For example, the dicarboxylic acid component may contain aliphatic dicarboxylic acids in addition to aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid.

[0063] Specific examples of the aliphatic dicarboxylic acid include linear or alicyclic dicarboxylic acids having 2 to 40 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, dimer acid, and cyclohexanedicarboxylic acid. Examples of the derivatives of the aliphatic dicarboxylic acids include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the above aliphatic dicarboxylic acids, and cyclic acid anhydrides of the above aliphatic dicarboxylic acids, such as succinic anhydride. Among these, the aliphatic dicarboxylic acids are preferably adipic acid, succinic acid, dimer acid, or mixtures thereof, and particularly preferably those containing succinic acid as the main component. The derivatives of the aliphatic dicarboxylic acids are more preferably methyl esters of adipic acid and succinic acid, or mixtures thereof.

[0064] The resin in the resin composition constituting the resin film containing recycled PET may be composed of only recycled PET, or may contain virgin PET in addition to recycled PET. The recycled PET film may be a single layer or may be a multilayer. When the resin film containing recycled PET is made into three layers, that is, the innermost layer / middle layer / outermost layer, it is preferable that the middle layer is made of only recycled PET or a mixed layer of recycled PET and virgin PET, and the innermost layer and the outermost layer on both sides are made of only virgin PET. In this way, by using only virgin PET for the innermost layer and the outermost layer, it is possible to prevent the recycled PET from appearing from the front or back surface of the resin film. Therefore, it is possible to ensure the hygiene of the laminate. When the resin film containing recycled PET is made into two layers, it is preferable that one layer is made of only recycled PET or a mixed layer of recycled PET and virgin PET, and the other layer is made of only virgin PET. When the resin film containing recycled PET is molded into a single layer by mixing recycled PET and virgin PET, there are a method of feeding them separately to a molding machine, a method of mixing them by dry blending, etc., and then feeding them. Among these, the method of mixing by dry blending is preferred from the viewpoint of ease of operation.

[0065] The resin composition constituting the resin film containing recycled polyethylene PET can contain various additives during or after the production process, as long as the properties are not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, release agents, antioxidants, ion exchange agents, and color pigments. The additives are preferably contained in the entire resin composition containing PET in an amount of 5% by mass to 50% by mass, preferably 5% by mass to 20% by mass.

[0066] A resin film containing recycled PET can be formed, for example, by filming using a T-die method. Specifically, after drying the above-mentioned PET, the resin composition is fed to a melt extruder heated to a temperature (Tm) to Tm+70°C above the melting point of PET to melt the resin composition, and extruded into a sheet from a die such as a T-die, and the extruded sheet is quenched and solidified by a rotating cooling drum, etc., to form a film. As the melt extruder, a single-screw extruder, a twin-screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.

[0067] The resin film containing recycled PET is preferably biaxially stretched. Biaxial stretching can be performed by a conventional method. For example, the film extruded onto the cooling drum as described above is then heated by roll heating, infrared heating, or the like, and stretched in the longitudinal direction to obtain a longitudinally stretched film. This stretching is preferably performed by utilizing the peripheral speed difference between two or more rolls. The longitudinal stretching is usually performed in a temperature range of 50°C to 100°C. The longitudinal stretching ratio is preferably 2.5 times to 4.2 times, depending on the required properties of the film application. If the stretching ratio is less than 2.5 times, the thickness unevenness of the PET film becomes large, making it difficult to obtain a good film. The longitudinally stretched film is then subjected to the respective processing steps of transverse stretching, heat setting, and heat relaxation in sequence to obtain a biaxially stretched film. The transverse stretching is usually performed in a temperature range of 50°C to 100°C. The transverse stretching ratio is preferably 2.5 times to 5.0 times, depending on the required properties of the application. If the stretching ratio is less than 2.5 times, the thickness of the film becomes uneven, making it difficult to obtain a good film, and if the stretching ratio exceeds 5.0 times, breakage is likely to occur during film formation. After the transverse stretching, heat setting is performed, and the preferred temperature range for heat setting is Tg+70 to Tm-10°C of PET. The heat setting time is preferably 1 second or more and 60 seconds or less. For applications requiring a reduction in the heat shrinkage rate, heat relaxation treatment may be performed as necessary.

[0068] The thickness of the resin film containing recycled PET is optional depending on the application, but is usually about 5 to 500 μm. The breaking strength of the resin film containing recycled PET is 5 kgf / mm in the MD direction. 2 More than 40kgf / mm 2 Below, 5kgf / mm in TD direction 2 More than 35kgf / mm 2 The elongation at break is 50% or more and 350% or less in the MD direction and 50% or more and 300% or less in the TD direction. The shrinkage percentage when left in a temperature environment of 150°C for 30 minutes is 0.1% or more and 5% or less.

[0069] Virgin PET may be fossil fuel polyethylene terephthalate (hereinafter also referred to as fossil fuel PET) or biomass PET. Here, "fossil fuel PET" refers to PET that has a diol derived from a fossil fuel as the diol component and a dicarboxylic acid derived from a fossil fuel as the dicarboxylic acid component. Recycled PET may be obtained by recycling a PET resin product formed using fossil fuel PET, or may be obtained by recycling a PET resin product formed using biomass PET.

[0070] <High stiffness PET film (tough PET film)> The high stiffness PET film contains polyester as a main component and has a loop stiffness of 0.0017 N / 15 mm or more in at least one direction. The high stiffness film has a loop stiffness of 0.0017 N or more in at least one of the machine direction (MD) or the transverse direction (TD). The high stiffness film may have a loop stiffness of 0.0017 N or more in both the machine direction (MD) and the transverse direction (TD).

[0071] Loop stiffness is a parameter that indicates the stiffness of a film. A method for measuring loop stiffness will be described below with reference to Figs. 17 to 22. The measurement method described below can be used not only for a single-layer film such as a stretched plastic film, but also for a film including multiple layers such as a vapor-deposited film and a laminated film. A vapor-deposited film is a film including a single-layer film such as a stretched plastic film and a vapor-deposited film formed on the single-layer film. A laminated film is a film including multiple films that are laminated together.

[0072] FIG. 17 is a plan view showing the test piece 40 and the loop stiffness measuring instrument 45, and FIG. 18 is a cross-sectional view of the test piece 40 and the loop stiffness measuring instrument 45 of FIG. 17 taken along line IV-IV. The test piece 40 is a rectangular film having a long side and a short side. In the present application, the length L1 of the long side of the test piece 40 is set to 150 mm, and the length L2 of the short side is set to 15 mm. As the loop stiffness measuring instrument 45, for example, No. 581 Loop Stiffness Tester (registered trademark) LOOP STIFFNESS TESTER DA type manufactured by Toyo Seiki Seisakusho Co., Ltd. can be used. The length L1 of the long side of the test piece 40 can be adjusted as long as the test piece 40 can be held by a pair of chuck parts 46 described later.

[0073] The loop stiffness measuring device 45 has a pair of chuck portions 46 for gripping a pair of ends in the long side direction of the test piece 40, and a support member 47 for supporting the chuck portions 46. The chuck portions 46 include a first chuck 461 and a second chuck 462. In the state shown in FIG. 17 and FIG. 18, the test piece 40 is placed on the pair of first chucks 461, and the second chuck 462 does not yet grip the test piece 40 between the first chuck 461 and the second chuck 462. As will be described later, during measurement, the test piece 40 is gripped between the first chuck 461 and the second chuck 462 of the chuck portions 46. The second chuck 462 may be connected to the first chuck 461 via a hinge mechanism.

[0074] When a film to be measured, such as a stretched plastic film, a vapor-deposited film, or a laminated film, is available in a state before the film is processed into a packaged product, the test piece 40 may be produced by cutting the film to be measured. Also, the test piece 40 may be produced by cutting a packaged product made from a packaging material, such as a packaging bag, and taking out the film to be measured.

[0075] A method for measuring the loop stiffness of the test piece 40 using the loop stiffness measuring device 45 will be described. First, as shown in FIG. 17 and FIG. 18, the test piece 40 is placed on the first chuck 461 of a pair of chuck parts 46 arranged with a gap L3 therebetween. In the present application, the gap L3 is set so that the length of the loop part 41 (hereinafter also referred to as the loop length) described later is 60 mm. The test piece 40 includes an inner surface 40x located on the first chuck 461 side and an outer surface 40y located on the opposite side of the inner surface 40x. When the test piece 40 is made of a packaging material, the inner surface 40x and the outer surface 40y of the test piece 40 coincide with the inner surface and the outer surface of the packaging material. When the loop part 41 described later is formed in the test piece 40, the inner surface 40x is located inside the loop part 41, and the outer surface 40y is located outside the loop part 41. 19, the second chuck 462 is placed on the test piece 40 so as to grip the end of the test piece 40 in the long side direction between the first chuck 461 and the second chuck 462. As shown in FIG.

[0076] Next, as shown in FIG. 20, at least one of the pair of chucks 46 is slid on the support member 47 in a direction in which the distance between the pair of chucks 46 is reduced. This allows the loop portion 41 to be formed in the test piece 40. The test piece 40 shown in FIG. 20 has the loop portion 41, a pair of intermediate portions 42, and a pair of fixing portions 43. The pair of fixing portions 43 are portions of the test piece 40 that are gripped by the pair of chucks 46. The pair of intermediate portions 42 are portions of the test piece 40 that are located between the loop portion 41 and the pair of intermediate portions 42. As shown in FIG. 20, the chuck portion 46 is slid on the support member 47 until the inner surfaces 40x of the pair of intermediate portions 42 come into contact with each other. This allows the loop portion 41 having a loop length of 60 mm to be formed. The loop length of the loop portion 41 is the length of the test piece 40 between position P1 where the surface of one second chuck 462 on the loop portion 41 side intersects with the test piece 40, and position P2 where the surface of the other second chuck 462 on the loop portion 41 side intersects with the test piece 40. When the thickness of the test piece 40 is ignored, the above-mentioned interval L3 is a value obtained by adding 2×t to the length of the loop portion 41, where t is the thickness of the second chuck 462 of the chuck portion 46.

[0077] Then, as shown in FIG. 21, the posture of the chuck portion 46 is adjusted so that the protruding direction Y of the loop portion 41 relative to the chuck portion 46 is horizontal. For example, the posture of the chuck portion 46 supported by the support member 47 is adjusted by moving the support member 47 so that the normal direction of the support member 47 is horizontal. In the example shown in FIG. 21, the protruding direction Y of the loop portion 41 coincides with the thickness direction of the chuck portion. Also, the load cell 48 is prepared at a position separated by a distance Z1 from the second chuck 462 in the protruding direction Y of the loop portion 41. In this application, the distance Z1 is set to 50 mm. Next, the load cell 48 is moved at a speed V by a distance Z2 shown in FIG. 21 toward the loop portion 41 of the test piece 40. The distance Z2 is set so that the load cell 48 contacts the loop portion 41 and then pushes the loop portion 41 toward the chuck portion 46 side, as shown in FIG. 21 and FIG. 22. In this application, the distance Z2 is set to 40 mm. In this case, the distance Z3 between the load cell 48 and the second chuck 462 of the chuck portion 46 when the load cell 48 is pressing the loop portion 41 towards the chuck portion 46 is 10 mm. The speed V at which the load cell 48 is moved was set to 3.3 mm / sec.

[0078] 22, the load cell 48 is moved by a distance Z2 toward the chuck portion 46, and in a state in which the load cell 48 is pressing into the loop portion 41 of the test piece 40, the value of the load applied to the load cell 48 from the loop portion 41 becomes stable, and then the value of the load is recorded. The value of the load thus obtained is used as the loop stiffness of the film constituting the test piece 40. In this application, unless otherwise specified, the environment during the measurement of the loop stiffness is a temperature of 23°C and a relative humidity of 50%.

[0079] By using a high stiffness film having a loop stiffness of 0.0017 N or more in at least one direction as a stretched plastic film, the puncture strength of the stretched plastic film can be increased, whereby in a laminate film including the high stiffness film, the puncture strength of the laminate film can be, for example, 13 N or more, more preferably 14 N or more, and even more preferably 15 N or more or 16 N or more.

[0080] An example of the high stiffness film is a high stiffness PET film containing 51% by mass or more of PET. The content of PET in the high stiffness PET film may be 80% by mass or more, 90% by mass or more, or 95% by mass or more. The thickness of the high stiffness film is preferably 5 μm or more, more preferably 7 μm or more. The thickness of the high stiffness film may be 10 μm or more, or 14 μm or more. The thickness of the high stiffness film is preferably 30 μm or less, may be 25 μm or less, or may be 20 μm or less.

[0081] Preferred mechanical properties of the high stiffness film are further described. The puncture strength of the high stiffness film is preferably 10N or more, more preferably 11N or more. The tensile strength of the high stiffness film in at least one direction is preferably 250MPa or more, more preferably 280MPa or more. For example, the tensile strength of the high stiffness film in the machine direction is preferably 250MPa or more, more preferably 280MPa or more. The tensile strength of the high stiffness film in the perpendicular direction is preferably 250MPa or more, more preferably 280MPa or more. The tensile elongation of the high stiffness film in at least one direction is preferably 130% or less, more preferably 120% or less. For example, the tensile elongation of the high stiffness film in the machine direction is preferably 130% or less, more preferably 120% or less. The tensile elongation of the high stiffness film in the perpendicular direction is preferably 120% or less, more preferably 110% or less. Preferably, the tensile strength of the high stiffness film divided by the tensile elongation in at least one direction is 2.0 [MPa / %] or more. For example, the tensile strength of the high stiffness film divided by the tensile elongation in the transverse direction (TD) is preferably 2.0 [MPa / %] or more, more preferably 2.2 [MPa / %] or more. The tensile strength of the high stiffness film divided by the tensile elongation in the machine direction (MD) is preferably 1.8 [MPa / %] or more, more preferably 2.0 [MPa / %] or more.

[0082] The heat shrinkage of the high stiffness film in at least one direction is preferably 0.7% or less, more preferably 0.5% or less. For example, the heat shrinkage of the high stiffness film in the machine direction is preferably 0.7% or less, more preferably 0.5% or less. The heat shrinkage of the high stiffness film in the perpendicular direction is preferably 0.7% or less, more preferably 0.5% or less. The heating temperature for measuring the heat shrinkage is 100°C, and the heating time is 40 minutes.

[0083] The Young's modulus of the high stiffness film in at least one direction is preferably 4.0 GPa or more, more preferably 4.5 GPa or more. For example, the Young's modulus of the high stiffness film in the machine direction is preferably 4.0 GPa or more, more preferably 4.5 GPa or more. The Young's modulus of the high stiffness film in the perpendicular direction is preferably 4.0 GPa or more, more preferably 4.5 GPa or more.

[0084] Young's modulus can be measured in accordance with JIS K7127, as with tensile strength and tensile elongation. As a measuring instrument, a tensile tester STA-1150 manufactured by Orientec Co., Ltd. can be used. As a test piece, a high stiffness film cut into a rectangular film having a width of 15 mm and a length of 150 mm can be used. The distance between a pair of chucks holding the test piece at the start of measurement is 100 mm, and the tensile speed is 300 mm / min. The length of the test piece can be adjusted as long as the test piece can be held by the pair of chucks. In this application, unless otherwise specified, the environment during measurement of Young's modulus is a temperature of 25°C and a relative humidity of 50%.

[0085] Even when a vapor deposition film is provided, the high stiffness film has mechanical properties equivalent to those of a single high stiffness film. For example, a high stiffness film provided with an aluminum oxide vapor deposition film 130b has a loop stiffness of 0.0017 N or more in at least one direction. Even when a primer layer is further provided on the vapor deposition film, the high stiffness film has mechanical properties equivalent to those of a single high stiffness film. For example, a high stiffness film provided with an aluminum oxide vapor deposition film and an organic coating layer has a loop stiffness of 0.0017 N or more in at least one direction.

[0086] In the manufacturing process of a high stiffness film, for example, a first stretching step is carried out in which a plastic film obtained by melting and molding a polyester is stretched 3 to 4.5 times in the machine direction and the perpendicular direction at 90°C to 145°C, respectively. Then, a second stretching step is carried out in which the plastic film is stretched 1.1 to 3.0 times in the machine direction and the perpendicular direction at 100°C to 145°C, respectively. Then, heat setting is carried out at a temperature of 190°C to 220°C. Then, relaxation treatment (treatment to reduce the film width) of about 0.2% to 2.5% is carried out at a temperature of 100°C to 190°C in the machine direction and the perpendicular direction. In these steps, a high stiffness film having the above-mentioned mechanical properties can be obtained by adjusting the stretch ratio, stretching temperature, heat setting temperature, and relaxation treatment rate.

[0087] A specific example of the high stiffness film is XP-55 manufactured by Toray Industries, Inc. This high stiffness film is biaxially stretched, contains 90% by mass or more of PET, and has a thickness of 16 μm. The measured loop stiffness of this high stiffness PET film was 0.0021 N in both the machine direction and the perpendicular direction. The Young's modulus of the high stiffness PET film in the machine direction was 4.8 GPa, and the Young's modulus of the high stiffness PET film in the perpendicular direction was 4.7 GPa. The tensile strength of the high stiffness PET film in the machine direction was 292 MPa, and the tensile strength of the high stiffness PET film in the perpendicular direction was 257 MPa. The tensile elongation of the high stiffness PET film in the machine direction was 107%, and the tensile elongation of the high stiffness PET film in the perpendicular direction was 102%. In this case, the tensile strength of the high stiffness PET film in the machine direction divided by the tensile elongation was 2.73 [MPa / %], and the tensile strength of the high stiffness PET film in the perpendicular direction divided by the tensile elongation was 2.52 [MPa / %]. The heat shrinkage of the high stiffness PET film in both the machine direction and perpendicular direction was 0.4%.

[0088] The substrate 120 may be a single layer or a multi-layer structure of two or more layers, and in the case of a multi-layer structure, the layers may be of the same composition or of different compositions. In the case of a multi-layer structure, each layer may be bonded to each other via an adhesive layer or the like.

[0089] [Aluminum oxide deposition film] Next, the aluminum oxide vapor deposition films 130b and 131b will be described. The aluminum oxide vapor deposition film contains aluminum oxide. In the aluminum oxide vapor deposition film, aluminum exists in a state in which it forms an element bond Al2O3, for example. The aluminum oxide vapor deposition film may further contain metal oxides such as silicon oxide, silicon nitride, silicon oxynitride, silicon carbide, magnesium oxide, titanium oxide, tin oxide, indium oxide, zinc oxide, and zirconium oxide, or metal nitrides and carbides thereof. Note that the "aluminum oxide vapor deposition film" in the present invention means a "vapor deposition film containing aluminum oxide" as described above, and may contain aluminum hydroxide Al2O4H in addition to aluminum oxide Al2O3.

[0090] The thickness of the aluminum oxide vapor deposition film is preferably more than 15 nm and less than 60 nm, and the lower limit is more preferably 18 nm or more, and particularly preferably 20 nm or more. The upper limit is more preferably 55 nm or less, and particularly preferably 50 nm or less. If it is more than 15 nm and less than 60 nm, high barrier properties, transparency, and flexibility can be achieved at the same time.

[0091] (TOF-SIMS analysis) The composition of the barrier film according to the present embodiment will be described in detail with reference to FIG. 12 of Comparative Example 1 and FIG. 13 of Example 1, which will be described later. FIG. 13 is an example of a graph analysis diagram showing the strength of elements and element bonds in a case where the barrier film in the first laminate 100A shown in FIG. 1 is etched from the surface side (the surface side opposite to the substrate) of the organic coating layer 130a by using time-of-flight secondary ion mass spectrometry (TOF-SIMS) to measure the elements and element bonds contained in the barrier film. FIG. 12 of Comparative Example 1 is an example of analysis in a layer structure of substrate / aluminum oxide vapor deposition film without an organic coating layer. The unit of the vertical axis (intensity) of the element and element bond graph is expressed by taking the common logarithm of the ion intensity. The unit of the horizontal axis (Et times) of the graph is the time of etching.

[0092] TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) is a method in which a primary ion beam from a primary ion gun is irradiated onto the surface of a solid sample to be analyzed, and the secondary ions sputtered and released from the sample surface are mass-separated and analyzed using their flight time difference (flight time is proportional to the square root of mass).

[0093] Here, by detecting the secondary ion intensity while the sputtering is proceeding, the concentration distribution of the detectable element in the depth direction of the sample surface can be obtained by converting the transition time into depth data for the ion intensity of the secondary ions, i.e., the ions of the detectable element or molecular ions bonded to the detectable element.

[0094] Then, the depth of the depression formed on the sample surface by the irradiation of primary ions is measured in advance using a surface roughness meter, and the average sputtering rate is calculated from the depression depth and transition time. Under the assumption that the sputtering rate is constant, the depth (sputtering amount) can be calculated from the irradiation time (i.e., transition time) or the number of irradiation cycles.

[0095] Specifically, the elements and element bonds of the organic coating layer 130a, the aluminum oxide deposition film 130b, and the substrate 120 are measured using a time-of-flight secondary ion mass spectrometer while soft etching is repeated at a constant speed from the outermost surface of the organic coating layer 130a (from the outermost surface of the aluminum oxide deposition film in FIG. 12) using a Cs (cesium) ion gun, and graphs of the measured elements and element bonds can be obtained. As a specific example, as shown in FIG. 12 and FIG. 13, at least the intensity derived from Al2O3, the intensity derived from Al2O4H, the intensity derived from C6, and the intensity derived from Al3 are detected from the barrier film according to this embodiment. The examples shown in FIG. 12 and FIG. 13 show examples in which the intensities of these four kinds of element bonds are measured.

[0096] In Fig. 12, the position of Et time T1 where the intensity of the graph of element C6 becomes half of the maximum intensity is taken as the interface between the plastic substrate and aluminum oxide, and the area from the barrier film surface (T0) to the interface T1 is taken as the aluminum oxide vapor deposition film (X in Fig. 12). In Fig. 12, the intensity peak derived from Al2O3 decreases on the substrate side. Therefore, the Et time where the intensity becomes half may be taken as the interface T1 between the substrate and the vapor deposition film.

[0097] In Fig. 13, first, as in the above, the position of Et time T1 where the intensity of the graph of element C6 is half of the maximum intensity is taken as the interface between the plastic substrate and the deposition film. Next, the position of Et time T0 where the intensity of the intensity derived from Si constituting the organic coating layer is half (of the maximum intensity) is taken as the interface between the organic coating film and aluminum oxide. Then, the period from T0 to T1 is taken as the aluminum oxide deposition film (X in Fig. 13).

[0098] 13, the intensity derived from Al2O3 has an upwardly convex peak, and the range in which this peak exists is the range of the aluminum oxide vapor deposition film. Therefore, the position of Et time T1 where the intensity peak derived from Al2O3 decreases on the substrate side and the intensity is halved may be taken as the interface between the plastic substrate and aluminum oxide, and next, the position of Et time T0 where the intensity peak derived from Al2O3 decreases on the organic coating layer 130a side and the intensity is halved may be taken as the interface between the organic coating layer 130a and aluminum oxide, and the region from T0 to T1 may be taken as the aluminum oxide vapor deposition film.

[0099] 12 and 13, the aluminum oxide vapor-deposited film has a maximum peak Tp of the intensity of the elemental bond Al2O4H. The region from Tp to the interface T1 is referred to as the transition region. In the present invention, the depth position Y of the maximum peak (Tp) with respect to X, which corresponds to the thickness of the vapor-deposited film, is preferably 50% to 99% or less, more preferably 60% to 99% or less, more preferably 70% to 99% or less, and particularly preferably 70% to 95% or less from the surface side (opposite side to the substrate side) of the vapor-deposited film. Also, the intensity I of the elemental bond Al2O3 at the position Tp P1 Strength of elemental bond Al2O4H to I P2 The ratio (I P2 / I P1 ) is 1.0 or more, preferably 1.0 or more and 4.0 or less, and more preferably 2.0 or more and 4.0 or less.

[0100] The maximum peak due to the element bond Al2O4H is 50% or more and 99% or less, that is, it is present closer to the substrate side, and the ratio (I P2 / I P1 ) to be 1.0 or more, the main region of Al2O4H exists on the substrate side of the evaporated film, and this configuration enables high barrier properties.

[0101] 12 and 13, the position 1 / 3 of the Et time from T0 to T1, that is, 1 / 3X, is defined as T2.

[0102] At this time, the strength of the element bond Al2O3 at T2 is I21 Strength of elemental bond Al2O4H to I 22 The ratio (I 22 / I 21 ) is 0.30 or less, preferably 0.20 or less, and more preferably 0.10 or less. As a result, in the surface vicinity region of the vapor-deposited film, the ratio of element bond Al2O4H is small, and a region mainly in the state of Al2O3 exists, so that the barrier performance can be improved. In this case, the barrier film has a structure of Al2O4 main region / Al2O4H main region / substrate from the film surface side, and this structure enables high barrier performance.

[0103] In addition, the strength of the element bond Al2O3 at T2 I 21 Strength of elemental bond Al2O4H to I 22 The ratio (I 22 / I 21 ) and the depth position of the maximum peak (Tp), and the intensity I of the element bond Al2O3 at the position Tp P1 Strength of elemental bond Al2O4H to I P2 The ratio (I P2 / I P1 ) can be adjusted by controlling the combination of the conditions of the pretreatment, particularly the oxygen plasma treatment, the conditions of the plasma-assisted treatment during deposition, and the oxygen concentration during deposition in forming the aluminum oxide vapor deposition film.

[0104] In addition, if the only purpose is to increase the barrier property, it is possible to obtain a high barrier property by adjusting the oxygen supply amount during deposition to a low level. In this case, in addition to Al2O3 and Al2O4H, the intensity peak T of Al3 derived from metallic aluminum is also increased. Al is detected, resulting in a barrier film with poor transparency (see Comparative Example 4, FIG. 16, described later). Therefore, in the barrier film of the present invention, an intensity peak derived from the element bond Al3 is not detected. Note that, "no intensity peak is detected" refers to the I Al / I Al2O3 The peak intensity ratio of the Al3-based barrier film to the Al3-based barrier film is 0.1 or less, and preferably 0.01 or less. The presence of the intensity peak derived from the element bond Al3 affects the transparency of the barrier film.* a * b * The color system is L * is preferably 99 or more and less than 100. * is preferably 0.00 or more and 0.50 or less, and more preferably 0.10 or more and 0.40 or less.

[0105] In the layer structure of FIG. 2, after performing TOF-SIMS analysis on the layer structure of substrate / deposited film 130b / organic coating layer 130a, which is the same layer structure as in FIG. 1, a layer structure of substrate / deposited film 130b / organic coating layer 130a / deposited film 131b / organic coating layer 131a is formed, and TOF-SIMS analysis is performed on the deposited film 131b / organic coating layer 131a from the organic coating layer 131a side to confirm that the respective barrier layers, that is, the deposited film 130b / organic coating layer 130a and the deposited film 131b / organic coating layer 131a, satisfy the above-mentioned range.

[0106] (Organic coating layer) The organic coating layers 130a, 131a laminated on the surfaces of the aluminum oxide vapor-deposited films 130b, 131b serve to mechanically and chemically protect the aluminum oxide vapor-deposited films and to improve the barrier performance of the laminated film having barrier properties. The organic coating layers will be described below.

[0107] The organic coating layer is formed by applying a barrier coating agent onto the aluminum oxide vapor deposition film and solidifying it. The barrier coating agent is composed of a metal alkoxide, a hydroxyl group-containing water-soluble resin, a silane coupling agent (if necessary), a sol-gel catalyst, an acid, etc.

[0108] As the metal alkoxide, the general formula R1 n M(OR 2 ) m(wherein, in the formula, R1 and R2 represent an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M), and examples of the metal atom represented by M of the metal alkoxide include silicon, zirconium, titanium, aluminum, and the like. For example, it is preferable to use an alkoxysilane in which M is Si.

[0109] The above alkoxysilane is, for example, one represented by the general formula Si(ORa)4 (wherein Ra represents a lower alkyl group). In the above, Ra may be a methyl group, an ethyl group, an n-propyl group, an n-butyl group, or the like. Specific examples of the above alkoxysilane include tetramethoxysilane Si(OCH3)4, tetraethoxysilane Si(OC2H5)4, tetrapropoxysilane Si(OC3H7)4, tetrabutoxysilane Si(OC4H9)4, and the like. The above alkoxides may be used in combination of two or more kinds.

[0110] Silane coupling agents having reactive groups such as vinyl, epoxy, methacryl, and amino groups can be used. In particular, organoalkoxysilanes having epoxy groups are suitable, and for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropyldimethylmethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyldimethylethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be used. The above-mentioned silane coupling agents may be used alone or in combination of two or more.

[0111] In particular, the crosslink density of the cured film of the organic coating layer using bifunctional organic compounds such as γ-glycidoxypropylmethyldimethoxysilane and γ-glycidoxypropylmethyldiethoxysilane is lower than that of the system using trialkoxysilane. Therefore, the cured film has excellent gas barrier properties and hot water treatment resistance, while also being flexible and has excellent bending resistance, so that the gas barrier properties of the packaging material using the barrier film are not easily deteriorated even after the Gelbo flex test.

[0112] The hydroxyl-containing water-soluble resin may be a polyvinyl alcohol resin or an ethylene-vinyl alcohol copolymer, or may be a combination of a polyvinyl alcohol resin and an ethylene-vinyl alcohol copolymer. In the organic coating layers 130a and 131a according to the present embodiment, a polyvinyl alcohol resin is preferred.

[0113] Generally, the polyvinyl alcohol resin can be one obtained by saponifying polyvinyl acetate. The polyvinyl alcohol resin can be a partially saponified polyvinyl alcohol resin in which several tens of percent of acetate groups remain, a completely saponified polyvinyl alcohol in which no acetate groups remain, or a modified polyvinyl alcohol resin in which OH groups have been modified. As the polyvinyl alcohol resin, it is necessary to use at least one that undergoes crystallization to improve the film hardness of the gas barrier coating film, and preferably has a saponification degree of 70% or more. In addition, any polyvinyl alcohol resin can be used as long as it has a polymerization degree within the range used in the conventional sol-gel method (about 100 to 5000). Examples of such polyvinyl alcohol resins include RS resin "RS-110 (saponification degree = 99%, polymerization degree = 1,000)" manufactured by Kuraray Co., Ltd. and "GOHSENOL NM-14 (saponification degree = 99%, polymerization degree = 1,400)" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0114] The ethylene-vinyl alcohol copolymer may be a saponified copolymer of ethylene and vinyl acetate, i.e., a product obtained by saponifying an ethylene-vinyl acetate random copolymer. For example, it may be a partially saponified product in which several tens of mol% of acetate groups remain, or a completely saponified product in which only a few mol% of acetate groups remain or no acetate groups remain, and is not particularly limited. However, from the viewpoint of barrier properties, it is preferable to use a saponification degree of 80% or more, more preferably 90% or more, even more preferably 95% to 100%, and particularly preferably 99% to 100%.

[0115] As the sol-gel catalyst, an acid or amine compound is preferable.

[0116] As the acid, for example, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. can be used.

[0117] The content of the acid is preferably 0.001 to 0.05 mol%, more preferably 0.01 to 0.03 mol%, based on the total molar amount of alkoxy groups in the metal alkoxide. If the content is less than 0.001%, the catalytic effect is too small, whereas if the content is more than 0.05 mol%, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0118] As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable. Specifically, for example, N,N-dimethylbenzylamine, tripropylamine, tributylamine, tripentylamine, etc. can be used. In particular, N,N-dimethylbenzylamine is preferable.

[0119] The content of the amine compound is preferably, for example, 0.01 to 1.0 part by mass, particularly 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. If the content is less than 0.01 part by mass, the catalytic effect is too small, whereas if the content is more than 1.0 part by mass, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0120] As the solvent, it is preferable to use water or alcohol such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropanol, or n-butanol.

[0121] The organic coating layer with barrier properties formed as described above has a layer thickness of 100 to 500 nm, which is preferable because the coating film does not crack and sufficiently covers the surface of the deposited film.

[0122] When the barrier coating agent contains a silane coupling agent, 5 to 10 parts by mass of a hydroxyl-containing water-soluble resin such as a polyvinyl alcohol resin and 1 to 10 parts by mass of a silane coupling agent can be used relative to 100 parts by mass of alkoxysilane. This allows the flexibility of the film to be maintained. In the above, if the silane coupling agent is used in an amount exceeding 20 parts by mass, the rigidity and brittleness of the barrier coating film formed increases, which is undesirable.

[0123] Furthermore, when no silane coupling agent is contained, the ratio of metal alkoxide can be reduced and the barrier properties can be improved by using 10 to 20 parts by mass of a hydroxyl group-containing water-soluble resin such as a polyvinyl alcohol resin per 100 parts by mass of alkoxysilane.

[0124] (Primer layer) The following primer layer can be used as the organic coating layer laminated on the surface of the aluminum oxide vapor deposition film. When the organic coating layer is a primer layer, it improves the adhesion when other layers are laminated on the aluminum oxide vapor deposition film, and also improves the barrier performance. The primer layer will be described below.

[0125] The primer layer is formed by applying a primer liquid containing a urethane resin and solidifying it, and may further contain a silane coupling agent and silica fine particles, if necessary.

[0126] The thickness of the primer layer after drying is preferably from 0.01 to 30 μm, and more preferably from 0.1 to 10 μm.

[0127] By including a urethane resin in the primer layer, the primer layer has appropriate elasticity or flexibility, and the influence of the pressure during printing or lamination on the inorganic vapor deposition layer can be reduced, and deterioration of the gas barrier property can be suppressed. As the urethane resin, any of the conventionally known polyester urethane resins and polyether urethane resins can be used. As such a urethane resin, a reaction product of a polyol such as a polyester polyol or a polyether polyol with a polyisocyanate can be used.

[0128] Examples of the polyester polyol include polyester polyols obtained by reacting a low molecular weight polyol with a polycarboxylic acid, polyester polyols obtained by ring-opening polymerization of a cyclic ester compound such as ε-caprolactone, and polyester polyols obtained by copolymerizing these. These polyester polyols can be used alone or in combination of two or more kinds.

[0129] Examples of low molecular weight polyols include aliphatic polyols having a molecular weight of about 50 to 300, such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol; polyols having an aliphatic cyclic structure, such as cyclohexanedimethanol; and polyols having an aromatic structure, such as bisphenol A and bisphenol F. Examples of polycarboxylic acids that can be used in the production of polyester polyols include aliphatic polycarboxylic acids, such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic polycarboxylic acids, such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof. In addition, polyester polyurethane polyols having urethane bonds in the molecular structure, which are obtained by modifying the above polyester polyols with polyisocyanates, can also be used as polyester polyols. These polyester polyols can be used alone or in combination of two or more.

[0130] The polyether polyol may be, for example, a product obtained by addition polymerization of an alkylene oxide using one or more compounds having two or more active hydrogen atoms as an initiator. Examples of the compound having two or more active hydrogen atoms include propylene glycol, trimethylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, glycerin, diglycerin, trimethylolethane, trimethylolpropane, water, hexanetriol, and the like. Examples of the alkylene oxide include propylene oxide, butylene oxide, styrene oxide, epichlorohydrin, tetrahydrofuran, and the like. In addition, as the polyether polyol, a polyether polyurethane polyol having a urethane bond in the molecular structure obtained by modifying the above polyether polyol with a polyisocyanate may be used. These polyether polyols may be used alone or in combination of two or more.

[0131] Examples of the polyisocyanate include polyisocyanates having an aliphatic cyclic structure such as cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate; aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, crude diphenylmethane diisocyanate, phenylene diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate; and aliphatic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate. Among these, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, and crude diphenylmethane diisocyanate are preferred. These polyisocyanates can be used alone or in combination of two or more kinds.

[0132] As the silane coupling agent, a conventionally known silane coupling agent can be used, and for example, the same silane coupling agent as that used in the above-mentioned gas barrier resin composition is preferably used. By including a silane coupling agent in the primer layer, the interlayer adhesion with the barrier coat layer can be improved.

[0133] As the silica fine particles, conventionally known silica can be used. In particular, when the urethane resin is polyether polyurethane, the primer layer contains silica fine particles, which can suppress blocking during winding in the production process of the gas barrier vapor deposition film.

[0134] (Film forming equipment) Next, an example of a film forming apparatus 10 used in the manufacturing method of a barrier film will be described. As shown in Fig. 4, the film forming apparatus 10 includes a substrate transport mechanism 11A for transporting the substrate 1 (same as the substrate 120), a plasma pretreatment mechanism 11B for performing plasma pretreatment on the surface of the substrate 1, and a film forming mechanism 11C for forming a vapor deposition film. In the example shown in Fig. 7, the film forming apparatus 10 further includes a decompression chamber 12. The decompression chamber 12 has a decompression mechanism, such as a vacuum pump described later, for adjusting the atmosphere in at least a part of the space inside the decompression chamber 12 to atmospheric pressure or lower.

[0135] In the example shown in Fig. 4, the decompression chamber 12 includes a substrate transport chamber 12A in which the substrate transport mechanism 11A is located, a plasma pretreatment chamber 12B in which the plasma pretreatment mechanism 11B is located, and a film formation chamber 12C in which the film formation mechanism 11C is located. The decompression chamber 12 is preferably configured to suppress the atmospheres in the respective chambers from mixing with each other. For example, as shown in Fig. 4, the decompression chamber 12 may be located between the substrate transport chamber 12A and the plasma pretreatment chamber 12B, between the plasma pretreatment chamber 12B and the film formation chamber 12C, and between the substrate transport chamber 12A and the film formation chamber 12C, and may have partition walls 35a to 35c that separate the respective chambers.

[0136] The substrate transfer chamber 12A, the plasma pretreatment chamber 12B, and the film formation chamber 12C will be described. The plasma pretreatment chamber 12B and the film formation chamber 12C are each provided in contact with the substrate transfer chamber 12A, and each has a portion connected to the substrate transfer chamber 12A. This allows the substrate 1 to be transferred between the substrate transfer chamber 12A and the plasma pretreatment chamber 12B, and between the substrate transfer chamber 12A and the film formation chamber 12C without being exposed to the atmosphere. For example, between the substrate transfer chamber 12A and the plasma pretreatment chamber 12B, the substrate 1 can be transferred through an opening provided in the partition wall 35a. The substrate transfer chamber 12A and the film formation chamber 12C have the same structure, and the substrate 1 can be transferred between the substrate transfer chamber 12A and the film formation chamber 12C.

[0137] The function of the decompression mechanism of the decompression chamber 12 will be described. The decompression mechanism of the decompression chamber 12 is configured to reduce the pressure of the atmosphere in the space in which at least the plasma pretreatment mechanism 11B or the film formation mechanism 11C of the film formation apparatus 10 is disposed to below atmospheric pressure. The decompression mechanism may be configured to reduce the pressure of each of the substrate transfer chamber 12A, the plasma pretreatment chamber 12B, and the film formation chamber 12C, which are partitioned by partition walls 35a to 35c, to below atmospheric pressure.

[0138] The configuration of the decompression mechanism of the decompression chamber 12 will be described. The decompression chamber 12 may have, for example, a vacuum pump connected to the plasma pretreatment chamber 12B. By adjusting the vacuum pump, the pressure in the plasma pretreatment chamber 12B when performing the plasma pretreatment described later can be appropriately controlled. In addition, the plasma supplied into the plasma pretreatment chamber 12B can be prevented from diffusing to other chambers by a method described later. The decompression mechanism of the decompression chamber 12 may have a vacuum pump connected to the film formation chamber 12C, similar to the vacuum pump connected to the plasma pretreatment chamber 12B. As the vacuum pump, a dry pump, a turbo molecular pump, a cryopump, a rotary pump, a diffusion pump, or the like can be used.

[0139] A substrate transport mechanism 11A for the substrate 1 of the film forming apparatus 10 according to this embodiment will be described together with the transport path of the substrate 1. The substrate transport mechanism 11A is a mechanism arranged in the substrate transport chamber 12A for transporting the substrate 1. In the example shown in FIG. 4, the substrate transport mechanism 11A has an unwinding roller 13 to which a roll-shaped original web of the substrate 1 is attached, a winding roller 15 for winding the substrate 1, and guide rolls 14a to 14d. The substrate 1 sent out from the substrate transport mechanism 11A is then transported by a pretreatment roller 20 (described later) arranged in the plasma pretreatment chamber 12B and a film formation roller 25 (described later) arranged in the film formation chamber 12C.

[0140] Although not shown, the substrate transport mechanism 11A may further include a tension pick-up roller. By including the tension pick-up roller in the substrate transport mechanism 11A, the substrate 1 can be transported while adjusting the tension applied to the substrate 1.

[0141] (Plasma pretreatment mechanism) The plasma pretreatment mechanism 11B will be described. The plasma pretreatment mechanism 11B is a mechanism for performing plasma pretreatment on the surface of the substrate 1. The plasma pretreatment mechanism 11B shown in FIG. 4 generates plasma P and performs plasma pretreatment on the surface of the substrate 1 using the generated plasma P. The plasma pretreatment activates the surface of the substrate 1, making it easier for nitrogen contained inside the substrate 1 to gather on the surface of the substrate 1, or making it easier for nitrogen contained in the environment surrounding the substrate 1 to be taken in by the surface of the substrate 1. Therefore, when a vapor deposition film is formed on the surface of the substrate 1 that has been subjected to plasma pretreatment, a peak of elemental bond CN can be formed at the interface between the substrate 1 and the vapor deposition film. The plasma pretreatment mechanism 11B shown in FIG. 4 has a pretreatment roller 20 arranged in the plasma pretreatment chamber 12B, an electrode unit 21 facing the pretreatment roller 20, and a magnetic field forming unit 23 that forms a magnetic field between the pretreatment roller 20 and the electrode unit 21.

[0142] The pretreatment roller 20 will be described. FIG. 5 is an enlarged view of the portion surrounded by the dashed line marked with the symbol VI in FIG. 4. Note that in FIG. 5, the power supply wiring 31 connecting the power source 32 shown in FIG. 4 and the electrode unit 21 described later, and the plasma P generated by the plasma pretreatment mechanism 11B are omitted. The pretreatment roller 20 has a rotation axis X. The pretreatment roller 20 is provided so that at least the rotation axis X is located in the plasma pretreatment chamber 12B partitioned by the partition walls 35a and 35b. The substrate 1 having a dimension in the direction of the rotation axis X is wound around the pretreatment roller 20. In the following description, the dimension of the substrate 1 in the direction of the rotation axis X is also referred to as the width of the substrate 1. The direction of the rotation axis X is also referred to as the width direction of the substrate 1.

[0143] As shown in FIG. 4, the pretreatment roller 20 may be provided so that a part of it is exposed to the substrate transport chamber 12A side. In the example shown in FIG. 4, the plasma pretreatment chamber 12B and the substrate transport chamber 12A are connected through an opening provided in the partition wall 35a, and a part of the pretreatment roller 20 is exposed to the substrate transport chamber 12A side through the opening. A gap is provided between the partition wall 35a between the substrate transport chamber 12A and the plasma pretreatment chamber 12B and the pretreatment roller 20, and the substrate 1 can be transported from the substrate transport chamber 12A to the plasma pretreatment chamber 12B through the gap. Although not shown, the pretreatment roller 20 may be provided so that the entirety thereof is located within the plasma pretreatment chamber 12B.

[0144] Although not shown, the pretreatment roller 20 may have a temperature adjustment mechanism that adjusts the surface temperature of the pretreatment roller 20. For example, the pretreatment roller 20 may have a temperature adjustment mechanism inside the pretreatment roller 20 that includes piping for circulating a temperature adjustment medium such as a refrigerant or a heat medium. The temperature adjustment mechanism adjusts the surface temperature of the pretreatment roller 20 to a target temperature within a range of, for example, −20° C. or more and 100° C. or less.

[0145] By providing the pretreatment roller 20 with a temperature adjustment mechanism, it is possible to prevent the substrate 1 from shrinking or being damaged by heat during plasma pretreatment.

[0146] The pretreatment roller 20 is made of a material containing at least one of stainless steel, iron, copper, and chromium. The surface of the pretreatment roller 20 may be treated with a hard chrome hard coat to prevent scratches. These materials are easy to process. In addition, by using the above materials as the material for the pretreatment roller 20, the thermal conductivity of the pretreatment roller 20 itself is increased, making it easier to control the temperature of the pretreatment roller 20.

[0147] The electrode unit 21 will be described. In the example shown in FIG. 4 and FIG. 5, the electrode unit 21 has a first surface 21c facing the pretreatment roller 20 and a second surface 21d located on the opposite side of the first surface 21c. In the example shown in FIG. 4 and FIG. 5, the electrode unit 21 is a plate-shaped member, and both the first surface 21c and the second surface 21d are flat. The electrode unit 21 generates plasma between the pretreatment roller 20 by applying an AC voltage between the electrode unit 21 and the pretreatment roller 20. The electrode unit 21 preferably forms an electric field between the electrode unit 21 and the pretreatment roller 20 so that the generated plasma moves in a direction perpendicular to the surface of the substrate 1 so as to move toward the surface of the substrate 1. This allows the substrate 1 to be pretreated efficiently. Therefore, when a vapor deposition film is formed on the surface of the substrate 1 that has been subjected to plasma pretreatment, the peak intensity H1 of the peak of elemental bond CN formed at the interface between the substrate 1 and the vapor deposition film can be made larger.

[0148] The number of electrode portions 21 is preferably 2 or more. The two or more electrode portions 21 are preferably arranged along the transport direction of the substrate 1. In the example shown in Fig. 4 and Fig. 5, an example is shown in which the film forming apparatus 10 has two electrode portions 21. In addition, the number of electrode portions 21 is, for example, 12 or less.

[0149] The effect of two or more electrode sections 21 arranged along the transport direction of the substrate 1 will be described. As described above, plasma is generated between the electrode section 21 and the pretreatment roller 20. The region in which plasma is generated expands as the dimension of the electrode section 21 in the transport direction increases. On the other hand, when the electrode section 21 is a flat plate-like member, the larger the dimension of the electrode section 21 in the transport direction, the greater the distance from the end of the first surface 21c, which is the surface of the electrode section 21 facing the pretreatment roller 20, to the pretreatment roller 20 in the transport direction, which reduces the processing ability by plasma.

[0150] In the film forming apparatus 10, two or more electrode units 21 are arranged along the transport direction of the substrate 1. Therefore, even if the dimension of the electrode unit 21 in the transport direction of the substrate 1 is small, plasma can be generated over a wide range in the transport direction. Furthermore, by reducing the dimension of the electrode unit 21, the distance from the end of the first surface 21c of the electrode unit 21 to the pretreatment roller 20 in the transport direction can be reduced, and plasma can be generated uniformly in the transport direction.

[0151] As shown in FIG. 4 and FIG. 5, the electrode unit 21 has a first end 21e and a second end 21f located on the first surface 21c of the electrode unit 21. The first end 21e is an end on the upstream side in the conveying direction of the substrate 1, and the second end 21f is an end on the downstream side in the conveying direction of the substrate 1. As described above, by reducing the dimension of the electrode unit 21 in the conveying direction of the substrate 1, the distance from the first end 21e and the second end 21f of the electrode unit 21 to the pre-treatment roller 20 in the conveying direction can be reduced. The dimension of the electrode unit 21 in the conveying direction of the substrate 1 corresponds to the angle θ shown in FIG. 5. The angle θ is the angle formed by a straight line passing through the first end 21e and the rotation axis X and a straight line passing through the second end 21f and the rotation axis X. The angle θ is preferably 20° or more and 90° or less, more preferably 60° or less, and even more preferably 45° or less. When the angle θ is within the above range, plasma can be generated uniformly in the transport direction between the electrode unit 21 and the pretreatment roller 20 when the first surface 21c of the electrode unit 21 is a flat surface.

[0152] There are no particular limitations on the material of the electrode portion 21 as long as it is conductive. Specifically, aluminum, copper, and stainless steel are preferably used as the material of the electrode portion 21.

[0153] The thickness L3 of the electrode unit 21 when viewed in a direction perpendicular to the first surface 21c of the electrode unit 21 is not particularly limited, but is, for example, 15 mm or less. When the thickness of the electrode unit 21 is the above value, a magnetic field can be effectively formed between the pre-treatment roller 20 and the electrode unit 21 by the magnetic field forming unit 23. The thickness L3 of the electrode unit 21 is, for example, 3 mm or more.

[0154] The magnetic field forming unit 23 will be described. As shown in Figs. 4 and 5, the magnetic field forming unit 23 is provided on the side of the electrode unit 21 opposite to the side facing the pretreatment roller 20. The magnetic field forming unit 23 is a member that forms a magnetic field between the pretreatment roller 20 and the electrode unit 21. The magnetic field between the pretreatment roller 20 and the electrode unit 21 contributes to the generation of higher density plasma, for example, when plasma is generated using the plasma pretreatment mechanism 11B. The magnetic field forming unit 23 shown in Figs. 4 and 5 has a first magnet 231 and a second magnet 232 provided on the second surface 21d of the electrode unit 21.

[0155] The number of the magnetic field forming units 23 is preferably 2 or more. When the plasma pretreatment mechanism 11B has two or more electrode units 21 and two or more magnetic field forming units 23, each of the two or more magnetic field forming units 23 is preferably provided on the side of each of the two or more electrode units 21 opposite to the side facing the pretreatment roller 20. In the example shown in Fig. 4 and Fig. 5, each of the two magnetic field forming units 23 is provided on the second surface 21d of each of the two electrode units 21.

[0156] The structure of the first magnet 231 and the second magnet 232 in the normal direction of the second surface 21d of the electrode unit 21 will be described. As shown in FIG. 4 and FIG. 5, the first magnet 231 and the second magnet 232 each have an N pole and an S pole. The symbol N shown in FIG. 4 and FIG. 5 indicates the N pole of the first magnet 231 or the second magnet 232. Also, the symbol S shown in FIG. 4 and FIG. 5 indicates the S pole of the first magnet 231 or the second magnet 232. One of the N pole or S pole of the first magnet 231 is located closer to the substrate 1 than the other. Also, the other of the N pole or S pole of the second magnet 232 is located closer to the substrate 1 than the other. In the example shown in FIG. 4 and FIG. 5, the N pole of the first magnet 231 is located closer to the substrate 1 than the S pole of the first magnet 231, and the S pole of the second magnet 232 is located closer to the substrate 1 than the N pole of the second magnet. Although not shown, the south pole of first magnet 231 may be located closer to substrate 1 than the north pole of first magnet 231, and the north pole of second magnet 232 may be located closer to substrate 1 than the south pole of second magnet 232.

[0157] Next, the structures of the first magnet 231 and the second magnet 232 in the planar direction of the second surface 21d of the electrode unit 21 will be described. Fig. 6 is a plan view of the electrode unit 21 and the magnetic field forming unit 23 shown in Fig. 4, viewed from the magnetic field forming unit 23 side. Fig. 7 is a cross-sectional view showing a cross section taken along line VIII-VIII in Fig. 6. In Fig. 6, direction D1 is the direction in which the rotation axis X of the pre-treatment roller 20 extends.

[0158] As shown in Fig. 6 and Fig. 7, the first magnet 231 has a first axial portion 231c. As shown in Fig. 6, the first axial portion 231c extends along the direction D1, i.e., along the rotation axis X of the pre-treatment roller 20. The first magnet 231 provided in one electrode unit 21 may have one first axial portion 231c, or may have two or more first axial portions 231c. In the example shown in Fig. 6, the first magnet 231 provided in one electrode unit 21 has one first axial portion 231c.

[0159] 6 and 7, the second magnet 232 has a second axial portion 232c. As shown in Fig. 6, the second axial portion 232c also extends along the direction D1, i.e., along the rotation axis X, similar to the first axial portion 231c.

[0160] Since both the first magnet 231 and the second magnet 232 include a portion extending along the rotation axis X, it is possible to increase the uniformity of the strength of the magnetic field formed around the substrate 1 in the width direction of the substrate 1. This makes it possible to increase the uniformity of the distribution density of the plasma formed around the substrate 1 in the width direction of the substrate 1.

[0161] The second magnet 232 provided on one electrode unit 21 may have one second axial portion 232c, or may have two or more second axial portions 232c. In the example shown in Fig. 6 and Fig. 7, the second magnet 232 provided on one electrode unit 21 has two second axial portions 232c. The two second axial portions 232c may be positioned so as to sandwich the first axial portion 231c in a direction D2 perpendicular to the rotation axis X in the planar direction of the second surface 21d of the electrode unit 21.

[0162] 7, the dimension L4 of the first axial portion 231c and the dimension L5 of the second axial portion 232c in the transport direction of the base material 1 are not particularly limited. In addition, the ratio of the dimension L4 of the first axial portion 231c to the dimension L5 of the second axial portion 232c in the transport direction of the base material 1 is not particularly limited. The dimension L4 of the first axial portion 231c and the dimension L5 of the second axial portion 232c may be equal, or the dimension L4 of the first axial portion 231c may be larger than the dimension L5 of the second axial portion 232c.

[0163] The distance L6 between the first axial portion 231c and the second axial portion 232c in the direction D2 is set so that a magnetic field generated by the first axial portion 231c and the second axial portion 232c is formed between the pre-treatment roller 20 and the electrode portion 21.

[0164] The second magnet 232 may surround the first magnet 231 when the magnetic field generating unit 23 is viewed along the normal direction of the second surface 21d of the electrode unit 21. For example, as shown in Fig. 6, the second magnet 232 may have two second axial portions 232c as well as two connection portions 232d provided to connect the two second axial portions 232c.

[0165] Examples of the types of magnets used as the magnetic field forming unit 23, such as the first magnet 231 and the second magnet 232, include permanent magnets such as ferrite magnets and rare earth magnets such as neodymium and samarium cobalt (samarium cobalt). Also, an electromagnet can be used as the magnetic field forming unit 23.

[0166] The magnetic flux density of the magnets of the magnetic field forming unit 23, such as the first magnet 231 and the second magnet 232, is, for example, 100 Gauss or more and 10,000 Gauss or less. If the magnetic flux density is 100 Gauss or more, a sufficiently strong magnetic field can be formed between the pretreatment roller 20 and the electrode unit 21, thereby generating plasma with a sufficiently high density, and a good pretreatment surface can be formed at high speed. On the other hand, in order to increase the magnetic flux density on the surface of the substrate 1 to more than 10,000 Gauss, an expensive magnet or magnetic field generating mechanism is required.

[0167] Although not shown, the plasma pretreatment mechanism 11B may have a plasma raw material gas supply unit. The plasma raw material gas supply unit supplies a gas serving as a raw material for plasma into the plasma pretreatment chamber 12B. The configuration of the plasma raw material gas supply unit is not particularly limited. For example, the plasma raw material gas supply unit is provided on the wall surface of the plasma pretreatment chamber 12B and includes a hole for ejecting the gas serving as a raw material for plasma. The plasma raw material gas supply unit may have a nozzle for ejecting the plasma raw material gas at a position closer to the substrate 1 than the wall surface of the plasma pretreatment chamber 12B. The plasma raw material gas supplied by the plasma raw material gas supply unit may be, for example, an inert gas such as argon, an active gas such as oxygen, nitrogen, carbon dioxide, or ethylene, or a mixed gas of these gases. As the plasma raw material gas, one kind of inert gas may be used alone, one kind of active gas may be used alone, or a mixed gas of two or more kinds of gases contained in the inert gas or active gas may be used. As the plasma raw material gas, a mixed gas of an inert gas such as argon and an active gas may be used. As an example, the plasma raw material gas supply unit supplies a mixed gas of argon (Ar) and oxygen (O2).

[0168] The plasma pretreatment mechanism 11B has a plasma density of, for example, 100 W·sec / m 2 More than 8000W sec / m 2 The following plasma is supplied between the pretreatment roller 20 and the electrode unit 21.

[0169] In the example shown in FIG. 4, the plasma pretreatment mechanism 11B includes a substrate transfer chamber 12A and a film formation chamber 1 The plasma pre-treatment chamber 12B is separated from the plasma pre-treatment chamber 2C by a partition wall. By separating the pretreatment chamber 12B from other regions such as the substrate transfer chamber 12A and the film formation chamber 12C, This makes it easier to independently adjust the atmosphere in the plasma pretreatment chamber 12B. Control of plasma raw material gas concentration in the space where the pretreatment roller 20 and the electrode unit 21 face each other This makes it easier to produce the laminated film, thereby improving productivity.

[0170] In this embodiment, the voltage applied between pretreatment roller 20 and electrode unit 21 of plasma pretreatment mechanism 11B is an AC voltage. By applying the AC voltage, plasma is generated between pretreatment roller 20 and electrode unit 21. Preferably, an electric field is formed such that the generated plasma moves toward the surface of substrate 1 in a direction perpendicular to the surface of substrate 1 by applying the AC voltage.

[0171] The value of the AC voltage applied between the pretreatment roller 20 and the electrode unit 21 is preferably 250 V or more and 1000 V or less. When the AC voltage has the above value, plasma with sufficient plasma density can be generated between the pretreatment roller 20 and the electrode unit 21. Here, the value of the AC voltage means the effective value Ve. The effective value Ve of the AC voltage can be calculated by the following formula, assuming that the maximum value of the AC voltage is Vm.

[0172]

number

[0173] The AC voltage applied between the pretreatment roller 20 and the electrode unit 21 has a frequency of, for example, 20 kHz or more and 500 kHz or less.

[0174] (Film forming mechanism) Next, the film formation mechanism 11C will be described. In the example shown in Fig. 4, the film formation mechanism 11C includes a film formation roller 25 and an evaporation mechanism 24 disposed in a film formation chamber 12C.

[0175] The film-forming roller 25 will be described below. The film-forming roller 25 is a roller that wraps around and transports the substrate 1 with the treated surface of the substrate 1 that has been pretreated in the plasma pretreatment mechanism 11B facing outward.

[0176] The material of the film-forming roller 25 will be described. The film-forming roller 25 is preferably formed from a material containing at least one of stainless steel, iron, copper, and chromium. The surface of the film-forming roller 25 may be subjected to a hard chrome hard coat treatment or the like to prevent scratches. These materials are easy to process. In addition, by using the above-mentioned materials as the material of the film-forming roller 25, the thermal conductivity of the film-forming roller 25 itself is increased, so that the temperature controllability is excellent when performing temperature control. The surface average roughness Ra of the film-forming roller 25 is, for example, 0.1 μm or more and 10 μm or less.

[0177] Although not shown, the film-forming roller 25 may have a temperature adjustment mechanism for adjusting the temperature of the surface of the film-forming roller 25. The temperature adjustment mechanism has, for example, a circulation path for circulating a cooling medium or a heat source medium inside the film-forming roller 25. The cooling medium (coolant) is, for example, an ethylene glycol aqueous solution, and the heat source medium (heat medium) is, for example, silicone oil. The temperature adjustment mechanism may have a heater installed at a position facing the film-forming roller 25. When the film-forming mechanism 11C forms a film by a deposition method, the temperature adjustment mechanism preferably adjusts the surface temperature of the film-forming roller 25 to a target temperature within a range of -20°C to 200°C in terms of restrictions on the heat resistance of related mechanical parts and versatility. By having the temperature adjustment mechanism in the film-forming roller 25, it is possible to suppress the temperature fluctuation of the substrate 1 caused by the heat generated during film formation.

[0178] The evaporation mechanism 24 will be described. FIG. 8 is an enlarged view of the portion surrounded by the dashed line marked with the symbol IX in FIG. 4, showing a specific form of the evaporation mechanism 24 that was omitted in FIG. 7, and showing an evaporation material supply unit 61 that supplies an evaporation material that was omitted in FIG. 4. Note that the decompression chamber 12 and the partition walls 35b and 35c are omitted in FIG. 8. The evaporation mechanism 24 is a mechanism that evaporates an evaporation material containing aluminum. The evaporated evaporation material adheres to the substrate 1, so that an evaporation film containing aluminum is formed on the surface of the substrate 1. The evaporation mechanism 24 in this embodiment employs a resistance heating type. In the example shown in FIG. 8, the evaporation mechanism 24 has a boat 24b. In this embodiment, the boat 24b has a power source (not shown) and a resistor (not shown) electrically connected to the power source. A plurality of boats 24b may be arranged in the width direction of the substrate 1.

[0179] As shown in Fig. 8, the film formation mechanism 11C may have a deposition material supply unit 61 that supplies a deposition material to the evaporation mechanism 24. Fig. 8 shows an example in which the deposition material supply unit 61 continuously feeds out an aluminum metal wire.

[0180] Although not shown, the film formation mechanism 11C has a gas supply mechanism. The gas supply mechanism is a mechanism that supplies gas between the evaporation mechanism 24 and the film formation roller 25. The gas supply mechanism supplies at least oxygen gas. The oxygen gas reacts with or bonds with an evaporation material such as aluminum that has evaporated from the evaporation mechanism 24 and is heading toward the substrate 1 on the film formation roller 25. This allows a vapor deposition film containing aluminum oxide to be formed on the surface of the substrate 1.

[0181] The film forming mechanism 11C also includes a plasma supply mechanism 50 that supplies plasma between the surface of the substrate 1 and the evaporation mechanism 24. In the example shown in FIG. 4 and FIG. 8, the plasma supply mechanism 50 has a hollow cathode 51. In this embodiment, the hollow cathode 51 is a cathode having a hollow portion that is partially open. The hollow cathode 51 can generate plasma in the hollow portion. In the example shown in FIG. 8, the hollow cathode 51 is provided so that the opening of the hollow portion of the hollow cathode 51 is located diagonally above the boat 24b. Although not shown, the plasma supply mechanism 50 according to this embodiment has an anode facing the opening, which draws out plasma from the opening of the hollow portion of the hollow cathode 51. The plasma supply mechanism 50 according to this embodiment can generate strong plasma between the surface of the substrate 1 and the evaporation mechanism 24 by generating plasma in the hollow portion of the hollow cathode 51 and drawing the plasma between the surface of the substrate 1 and the evaporation mechanism 24 by the opposing anode. The position of the opposing anodes is not particularly limited as long as the opposing anodes can draw out plasma from the opening of the cavity of the hollow cathode 51 and supply plasma between the surface of the substrate 1 and the evaporation mechanism 24. In this embodiment, a case where the opposing anodes are arranged on both sides of the boat 24b in the width direction of the substrate 1 will be described. In this case, the film formation mechanism 11C has a plurality of boats 24b and a plurality of opposing anodes, and the plurality of boats 24b and the plurality of opposing anodes may be arranged alternately in the width direction of the substrate 1. Although not shown, the plasma supply mechanism 50 may have a raw material supply device that supplies plasma raw material gas at least into the cavity of the hollow cathode 51. As the plasma raw material gas supplied by the raw material supply device, for example, a gas similar to the gas that can be used as the plasma raw material gas supplied by the plasma raw material gas supply unit of the plasma pretreatment mechanism 11B can be used.

[0182] By performing plasma assist during deposition by supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24 using the plasma supply mechanism 50, the aluminum and oxygen gas evaporated in the evaporation mechanism 24 can be activated, and the reaction or bonding between the aluminum and the oxygen gas can be promoted. This can increase the ratio of aluminum present as aluminum oxide in the evaporated film formed on the surface of the substrate 1, and stabilize the properties of the evaporated film.

[0183] Although not shown, the film forming apparatus 10 may include a substrate charge removal unit that performs post-processing to remove charge generated on the substrate 1 due to film formation by the film formation mechanism 11C, in a portion of the substrate transport chamber 12A that is located downstream of the film formation chamber 12C in the transport direction of the substrate 1. The substrate charge removal unit may be provided so as to remove charge from one side of the substrate 1, or may be provided so as to remove charge from both sides of the substrate 1.

[0184] The device used as the substrate charge removal section for performing post-treatment on the substrate 1 is not particularly limited, but for example, a plasma discharge device, an electron beam irradiation device, an ultraviolet ray irradiation device, a static elimination bar, a glow discharge device, a corona treatment device, etc. can be used.

[0185] When performing post-treatment by forming a discharge using a plasma treatment device or a glow discharge device, a discharge gas such as argon, oxygen, nitrogen, helium, or a mixture of these gases is supplied near the substrate 1, and post-treatment can be performed using any discharge method such as alternating current (AC) plasma, direct current (DC) plasma, arc discharge, microwave, surface wave plasma, etc. In a reduced pressure environment, it is most preferable to perform post-treatment using a plasma discharge device.

[0186] The substrate charge removal section is provided in a portion of the substrate transport chamber 12A that is located downstream of the film formation chamber 12C in the transport direction of the substrate 1, and the charge on the substrate 1 is removed, so that the substrate 1 can be transported by quickly separating it from the film formation roller 25 at a predetermined position. This enables stable substrate transport, prevents damage to the substrate 1 or deterioration in quality due to charging, and improves post-processing suitability by improving the wettability of the front and back surfaces of the substrate.

[0187] (power supply) In the example shown in FIG. 4, the film forming apparatus 10 further includes a power source 32 electrically connected to the pretreatment roller 20 and the electrode unit 21. In the example shown in FIG. 7, the power source 32 is electrically connected to the pretreatment roller 20 and the electrode unit 21 via the power supply wiring 31. The power source 32 is, for example, an AC power source. When the power source 32 is an AC power source, the power source 32 can apply an AC voltage having a frequency of, for example, 20 kHz or more and 500 kHz or less between the pretreatment roller 20 and the electrode unit 21. The input power that can be applied by the power source 32 (power that can be applied per 1 m width of the electrode unit 21 in the width direction of the substrate 1) is not particularly limited, but is, for example, 0.5 kW / m or more and 20 kW / m or less. The pretreatment roller 20 may be installed at an electrically earth level or at an electrically floating level.

[0188] (Barrier film manufacturing method) Next, a method for manufacturing the barrier film shown in Fig. 1 and Fig. 2 using the above-mentioned film forming apparatus 10 will be described. First, a film forming method for forming a vapor deposition film on the surface of the substrate 1 will be described. In film formation using the film forming apparatus 10, a plasma pretreatment step of performing plasma pretreatment on the surface of the substrate 1 using the plasma pretreatment mechanism 11B and a film formation step of forming a vapor deposition film on the surface of the substrate 1 using the film formation mechanism 11C are performed while the substrate 1 is transported along the above-mentioned transport path of the substrate 1. The transport speed of the substrate 1 is preferably 200 m / min or more, and more preferably 400 m / min or more and 1000 m / min or less.

[0189] (Plasma pretreatment process) The plasma pretreatment step is carried out, for example, by the following method. First, plasma raw material gas is supplied into the plasma pretreatment chamber 12B. Next, the above-mentioned AC voltage is applied between the pretreatment roller 20 and the electrode unit 21. When applying the AC voltage, input power control or impedance control may be performed.

[0190] The plasma raw material gas supplied in the pretreatment is oxygen alone or a mixture of oxygen gas and an inert gas, which is supplied from a gas reservoir while measuring the flow rate of the gas through a flow rate controller. The inert gas may be one or a mixture of two or more gases selected from the group consisting of argon, helium, and nitrogen.

[0191] In the plasma treatment, the mixing ratio of oxygen gas to the inert gas, that is, oxygen gas / inert gas, is preferably 6 / 1 to 1 / 1, and more preferably 5 / 2 to 3 / 2.5.

[0192] By setting the mixing ratio to 6 / 1 to 1 / 1, the energy required for forming the evaporated aluminum film on the resin substrate is increased, and by setting the ratio to 5 / 2 to 3 / 2, the degree of oxidation of the evaporated aluminum oxide film is increased, ensuring adhesion between the evaporated aluminum oxide film and the substrate.

[0193] Application of the AC voltage generates plasma simultaneously with glow discharge, and plasma P is densified between pretreatment roller 20 and magnetic field forming unit 23. In this manner, plasma P can be supplied between pretreatment roller 20 and magnetic field forming unit 23. This plasma P can be used to perform plasma (ion) pretreatment on the surface of substrate 1.

[0194] Plasma intensity per unit area in plasma processing is 50 W·sec / m 2 More than 8000W sec / m 2 Less than 50W sec / m 2 Below this, no effect of plasma pretreatment was observed, and below 8000W·sec / m 2Above this level, the resin substrate tends to deteriorate due to the plasma, such as wear, damage, discoloration, and burning. In particular, the plasma intensity for plasma pretreatment to form an aluminum oxide layer should be 100 W·sec / m 2 More than 1000W sec / m 2 The following is preferred:

[0195] The air pressure in plasma pretreatment chamber 12B when an AC voltage is applied between pretreatment roller 20 and electrode unit 21 is reduced to below atmospheric pressure by decompression chamber 12. In this case, the air pressure in plasma pretreatment chamber 12B is adjusted, for example, so that a glow discharge can be generated between pretreatment roller 20 and electrode unit 21 by application of an AC voltage. The degree of vacuum in plasma pretreatment chamber 12B when an AC voltage is applied between pretreatment roller 20 and electrode unit 21 can be set and maintained at about 0.1 Pa or more and 100 Pa or less, and in particular, 1 Pa or more and 20 Pa or less is preferable.

[0196] The function of the magnetic field forming unit 23 in the plasma pretreatment step will now be described. The magnetic field forming unit 23 forms a magnetic field between the pretreatment roller 20 and the electrode unit 21. The magnetic field can act to capture and accelerate electrons present between the pretreatment roller 20 and the electrode unit 21. As a result, in the region where the magnetic field is formed, it is possible to increase the frequency of collisions between the electrons and the plasma raw material gas, increase the density of the plasma, and localize it, thereby improving the efficiency of the plasma pretreatment.

[0197] (Film forming process) In the film formation step, a film is formed using the film formation mechanism 11C on the surface of the substrate 1. As an example of the film formation step, a case will be described in which an aluminum oxide vapor deposition film is formed using the film formation mechanism 11C having an evaporation mechanism 24 shown in FIG.

[0198] First, an evaporation material containing aluminum is supplied into the boat 24b of the evaporation mechanism 24 so as to face the deposition roller 25. An aluminum metal wire can be used as the evaporation material. In the example shown in Fig. 8, the evaporation material is supplied to the boat 24b by continuously feeding the aluminum metal wire into the boat 24b using an evaporation material supply unit 61.

[0199] Aluminum is evaporated in the boat 24b by heating. For convenience, FIG. 8 illustrates evaporated aluminum vapor 63. The oxygen gas for oxidizing aluminum may be supplied as oxygen alone or as a mixed gas with an inert gas such as argon, but by controlling the amount of oxygen, both barrier properties and transparency can be achieved. The degree of vacuum at this time is preferably 0.05 Pa or more and 8.00 Pa or less.

[0200] Furthermore, a method for supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24 by the plasma supply mechanism 50, i.e., plasma assist during deposition, will be described. In this embodiment, plasma is generated within the cavity of the hollow cathode 51 of the plasma supply mechanism 50. Next, a discharge is generated between the hollow cathode 51 and the opposing anode, and the plasma within the cavity of the hollow cathode 51 is drawn between the surface of the substrate 1 and the evaporation mechanism 24.

[0201] In this embodiment, the discharge generated between hollow cathode 51 and the opposing anode is an arc discharge. The arc discharge means a discharge with a current value of, for example, 10 A or more.

[0202] By evaporating aluminum while supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24, plasma is supplied to the aluminum vapor 63. Supplying plasma can promote the reaction or bonding between the aluminum vapor 63 and oxygen gas. This allows the aluminum vapor 63 to be oxidized before it reaches the surface of the substrate 1. The evaporated and oxidized aluminum adheres to the substrate 1, forming an aluminum oxide vapor deposition film on the surface of the substrate 1, and the barrier film shown in FIG. 1 can be manufactured.

[0203] The plasma raw material gas supplied by the plasma supply mechanism 50 is preferably oxygen alone or a mixed gas of oxygen gas and an inert gas.

[0204] In this embodiment, a plasma pretreatment step is performed before the film formation step, in which plasma is supplied to the surface of the substrate 1. In the plasma pretreatment step, an AC voltage is applied between the electrode unit 21 and the pretreatment roller 20. In addition, a magnetic field is generated in the space between the electrode unit 21 and the pretreatment roller 20 by using the magnetic field forming unit 23 located on the side of the surface of the electrode unit 21 opposite to the surface facing the pretreatment roller 20. Therefore, plasma can be efficiently generated in the space between the electrode unit 21 and the pretreatment roller 20, and the plasma can be made to perpendicularly enter the surface of the substrate 1 wound around the pretreatment roller 20. Therefore, the adhesion between the film formed in the film formation step and the substrate 1 can be improved.

[0205] (Organic coating layer formation process) Examples of the means for forming the organic coating layer by coating include roll coating such as a gravure roll coater, spray coating, spin coating, dipping, brushing, bar coding, and applicators. The organic coating layer may be formed by one or more coatings. The above coating operation may be further repeated on the first coating film to form multiple coating films consisting of two or more layers. Furthermore, the film is heated at a temperature of 20 to 200°C and below the melting point of the plastic substrate, preferably at a temperature in the range of 50 to 180°C, for 3 seconds to 10 minutes. This allows the organic coating layer to be formed on the aluminum oxide vapor deposition film.

[0206] [Anti-reflection layer and / or anti-glare layer] The anti-reflection layer and / or anti-glare layer 160 will be described below. The anti-reflection layer and / or anti-glare layer 160 may be an anti-glare layer, an anti-reflection layer, or an anti-glare layer and an anti-reflection layer that combines the functions of an anti-reflection layer and an anti-glare layer. In Figures 1 to 3, an anti-glare layer and an anti-reflection layer including a resin 161 and particles 162 are shown as an example.

[0207] <Anti-glare layer> The antiglare layer is also called an AG layer or an antiglare layer, and has antiglare properties. For example, the antiglare layer has surface irregularities or internal scattering properties, thereby exhibiting antiglare properties and improving contrast in bright areas. In addition, by having an antiglare layer, it is possible to suppress the occurrence of glare and the like when used in a reflective display device for electronic paper or the like. In order to scatter or diffuse light, it is essential to roughen the light incident surface. Examples of this roughening treatment include a method of directly roughening the substrate surface by a sandblasting method, an embossing method, or the like, a method of providing a roughened layer on the substrate surface, which contains inorganic fillers such as silica or organic fillers such as resin particles in a resin that is cured by radiation, heat, or a combination thereof, and a method of forming a porous film with a sea-island structure on the substrate surface.

[0208] The material for forming the antiglare layer is not particularly limited as long as it satisfies the above-mentioned refractive index and can form a layer having an uneven surface or internal scattering properties, and examples thereof include materials containing light-transmitting fine particles and a binder component.

[0209] The light-transmitting fine particles may be organic or inorganic. From the viewpoint of ensuring the transparency of the antiglare layer, organic fine particles, particularly acrylic fine particles, are preferred. The acrylic fine particles are not particularly limited, and examples thereof include isocyanate compounds, ester compounds, copolymers of acrylic monomer components, or copolymerizable monomers with these. Examples of the copolymers of the acrylic monomer components and monomers copolymerizable with these include methyl methacrylate-styrene copolymers.

[0210] Examples of inorganic fine particles include amorphous silica and inorganic silica beads.

[0211] The light-transmitting fine particles may be primary particles or secondary particles. The light-transmitting fine particles may be used not only as one type but also as a mixture of two or more types having different components depending on the purpose. It is preferable to use one to three types.

[0212] It is preferable that 80% or more (preferably 90% or more) of the total light-transmitting fine particles are within the range of the average particle size ±300 nm, which can improve the uniformity of the uneven shape of the antiglare layer.

[0213] The content of the light-transmitting fine particles in the antiglare layer is preferably within a range of 5% by mass to 40% by mass, more preferably within a range of 5% by mass to 20% by mass, based on the total solid mass of the antiglare layer. If the content is less than the range, sufficient antiglare properties cannot be imparted, whereas if the content exceeds the range, the film strength may decrease.

[0214] The binder component used in the antiglare layer provides the antiglare layer with film-forming properties. The binder component is preferably a curable organic resin, and is preferably a light-transmitting resin that transmits light when formed into a coating film. Specific examples of the binder include an ionizing radiation curable resin that is cured by ionizing radiation, typically ultraviolet light or electron beams, a mixture of an ionizing radiation curable resin and a solvent-drying resin (such as a thermoplastic resin that can be turned into a coating by simply drying the solvent used to adjust the solid content during coating), and a thermosetting resin, and preferably an ionizing radiation curable resin.

[0215] Examples of ionizing radiation curable resins include compounds having radical polymerizable functional groups such as (meth)acrylate groups, such as (meth)acrylate-based monomers, or polymers having monomers introduced into a polymer skeleton. More specifically, examples of (meth)acrylate-based monomers include ethyl (meth)acrylate, ethylhexyl (meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Examples of polymers having a monomer introduced into a polymer skeleton include polymers having a polymer skeleton of polyester resin, polyether resin, epoxy resin, urethane resin, alkyd resin, spiroacetal resin, polybutadiene resin, polythiolpolyene resin, polyhydric alcohol, fluorene resin, etc., and having a (meth)acrylate group introduced into the polymer skeleton. Examples other than the (meth)acrylate-based compound include monofunctional or polyfunctional monomers such as styrene, methylstyrene, N-vinylpyrrolidone, etc., or compounds having a cationic polymerizable functional group such as oligomers or prepolymers of bisphenol-type epoxy compounds, novolac-type epoxy compounds, aromatic vinyl ethers, aliphatic vinyl ethers, etc.

[0216] The antiglare layer may contain, as necessary, antiglare fine particles, a leveling agent, a polymerization initiator, a curing agent, a crosslinking agent, an ultraviolet blocking agent, an ultraviolet absorbing agent, etc. From the viewpoint of improving coating stability, slipperiness, anti-contamination properties, and abrasion resistance, it is preferable to contain a leveling agent such as a fluorine-based or silicone-based agent.

[0217] The antiglare layer can be formed, for example, by applying a coating liquid for forming the antiglare layer, drying it, and curing it as necessary. The average thickness of the antiglare layer is preferably within a range of 1 μm to 10 μm.

[0218] <Anti-reflection layer> The anti-reflection layer, also known as the AR layer or anti-reflection layer, has the function of preventing reflection of the background, whitening of the image, and reduction in image contrast caused by specular reflection of external light on the viewing surface when used in a reflective display device such as electronic paper.

[0219] The anti-reflection layer is made by laminating materials with high and low refractive indexes alternately, multi-layering (multi-coating) so that the outermost surface is a low refractive index layer, and by canceling out the reflected light at the interface between each layer through interference, it is possible to suppress surface reflection and obtain a good anti-reflection effect. This anti-reflection layer is usually formed by a gas phase method in which low refractive index materials such as MgF2 and SiO2 and high refractive index materials such as TiO2 and ZrO2 are alternately deposited by deposition or the like.

[0220] In order to improve the anti-reflection effect, the refractive index of the low refractive index layer disposed on the outermost surface side of the anti-reflection layer is preferably 1.49 or less. Examples of materials having these characteristics include inorganic low-reflection materials obtained by forming inorganic materials such as LiF (refractive index n=1.4), MgF2 (refractive index n=1.4), 3NaF·AlF3 (refractive index n=1.4), AlF3 (refractive index n=1.4), Na3AlF6 (refractive index n=1.33), and SiO2 (refractive index n=1.45) into fine particles and incorporating them into acrylic resins, epoxy resins, etc., and organic low-reflection materials such as fluorine-based and silicone-based organic compounds, thermoplastic resins, thermosetting resins, and radiation-curing resins.

[0221] Furthermore, a material obtained by mixing a sol in which ultrafine silica particles of 5 to 30 nm are dispersed in water or an organic solvent with a fluorine-based film-forming agent can also be used. The sol in which ultrafine silica particles of 5 to 30 nm are dispersed in water or an organic solvent can be a known silica sol obtained by condensing active silicic acid, which is known to be obtained by a method of de-alkalizing alkali metal ions in an alkali silicate by ion exchange or the like, or a method of neutralizing an alkali silicate with a mineral acid, a known silica sol obtained by hydrolyzing and condensing an alkoxysilane in an organic solvent in the presence of a basic catalyst, or an organic solvent-based silica sol (organosilica sol) obtained by replacing the water in the aqueous silica sol with an organic solvent by a distillation method or the like. These silica sols can be used in either an aqueous or organic solvent system. When producing an organic solvent-based silica sol, it is not necessary to completely replace the water with an organic solvent. The silica sol contains a solid content of 0.5 to 50% by weight as SiO2. Various structures of ultrafine silica particles in the silica sol can be used, such as spherical, needle-like, and plate-like. As the film-forming agent, alkoxysilane, hydrolysates of metal alkoxides or metal salts, fluorine-modified polysiloxane, and the like can be used.

[0222] [Support] In the laminate according to the present embodiment, as shown in Fig. 3, a support 150 may be disposed between the barrier film and the antireflection layer and / or antiglare layer 160. The support 150 is a layer mainly containing a resin, and the resin may be the same as the resin described for the substrate 120, but is not limited thereto and may be glass.

[0223] 3, the thickness of the support 150 is preferably more than 25 μm and not more than 200 μm, more preferably 38 μm or more and 175 μm or less, and even more preferably 50 μm or more and 150 μm or less. By making the thickness of the support 150 more than 25 μm and not more than 200 μm, the flexibility of the laminate is improved, and the handling properties when bonding it to other members of the display device are improved.

[0224] In order to avoid blocking of light from the light source, the support preferably has a high total light transmittance measured according to JIS K 7361. Specifically, the support preferably has a total light transmittance of 85% or more, more preferably 90% or more, measured according to JIS K 7361. In this specification, the term "transparent" is defined as above.

[0225] [Adhesive layer] As shown in Fig. 3, the laminate according to this embodiment may have an adhesive layer 140 disposed between the barrier film and a support 150. The adhesive layer refers to a pressure-sensitive adhesive layer or an adhesive layer. Examples of adhesives that can be used to form the adhesive layer 140 include polyvinyl acetate adhesives, homopolymers of ethyl, butyl, 2-ethylhexyl ester of acrylic acid, and the like, and polyacrylic acid ester adhesives made of copolymers of these with methyl methacrylate, acrylonitrile, styrene, and the like, cyanoacrylate adhesives, ethylene copolymer adhesives made of copolymers of ethylene with monomers such as vinyl acetate, ethyl acrylate, acrylic acid, methacrylic acid, and the like, cellulose adhesives, polyester adhesives, polyamide adhesives, polyimide adhesives, amino resin adhesives made of urea resin or melamine resin, and the like, phenol resin adhesives, epoxy adhesives, polyurethane adhesives, reactive (meth)acrylic adhesives, rubber adhesives made of chloroprene rubber, nitrile rubber, styrene-butadiene rubber, and the like, silicone adhesives, and inorganic adhesives made of alkali metal silicates, low-melting point glass, and the like.

[0226] The adhesive constituting the adhesive layer is not particularly limited as long as it has the desired adhesive strength, and examples thereof include acrylic, urethane, rubber, and silicone adhesives. Among these, acrylic adhesives are preferred because they are excellent in durability such as heat resistance and transparency, and are low-cost. Examples of acrylic adhesives include acrylic ester copolymers obtained by copolymerizing acrylic esters with other monomers. Examples of acrylic esters include ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, hydroxyethyl acrylate, propylene glycol acrylate, acrylamide, and glycidyl acrylate, and these may be used alone or in combination of two or more.

[0227] Examples of the other monomers include methyl acrylate, methyl methacrylate, styrene, acrylonitrile, vinyl acetate, acrylic acid, methacrylic acid, itaconic acid, hydroxylethyl acrylate, hydroxylethyl methacrylate, propylene glycol acrylate, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, n-ethylhexyl methacrylate, and the like. These may be used alone or in combination of two or more kinds.

[0228] The composition system of the adhesive layer may be any of the composition forms such as aqueous type, solution type, emulsion type, dispersion type, etc., and the properties may be any of the forms such as film / sheet type, powder type, solid type, etc., and further, the adhesive mechanism may be any of the forms such as chemical reaction type, solvent volatilization type, heat melting type, heat pressure type, etc.

[0229] The adhesive layer can be applied by, for example, roll coating, gravure coating, knife coating, dip coating, spray coating, other coating methods, or printing methods, and the coating amount is 0.1 g / m 2 More than 10g / m 2The following (dry state) is desirable.

[0230] Instead of the adhesive layer made of the adhesive, a resin layer made of, for example, a thermosetting resin or a thermoplastic resin containing a crosslinking agent, etc. may be laminated. Furthermore, a bonding method using extrusion lamination may be used in which a thermoplastic resin such as EVA, ionomer, polyvinyl butyral (PVB), polyethylene resin, etc. is melted and the molten thermoplastic resin is extruded and laminated.

[0231] <<Reflective display device>> A reflective display device including the above-mentioned first laminates 100A and 100B and second laminates 100C and 100D will be described with reference to FIGS. Fig. 9 is a cross-sectional view showing an example of a reflective display device according to an embodiment of the present invention. In Fig. 9, a reflective display device 200A, which is electronic paper, includes a display medium layer 110 including display media 112 and 113 dispersed in a dispersion medium 111, a transparent electrode 170 disposed on the viewing side via the display medium layer 110, and a back electrode 180 disposed on the back side opposite the viewing side via the display medium layer 110. The transparent electrode 170 is laminated with the first laminate 100A via an adhesive layer 140, and is disposed so that the anti-reflection layer and / or anti-glare layer 160 of the first laminate 100A is on the outside, i.e., the outermost surface on the viewing side, and is the light output side.

[0232] [Transparent electrode] The transparent electrode 170 is disposed so that its electrode portion faces the display medium layer 110. The material of the transparent electrode 170 used in the present invention is not particularly limited as long as it is a conductive material capable of forming a transparent electrode, and examples of the material that can be used include conductive oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), tin oxide, zinc oxide, indium oxide, and aluminum zinc oxide (AZO), metals such as Au and Ni, and conductive polymers such as polyaniline, polyacetylene, polyalkylthiophene derivatives, and polysilane derivatives, among which ITO is preferably used.

[0233] The thickness of the transparent electrode used in the present invention is not particularly limited as long as it can function as a transparent electrode, but it is preferably within the range of 15 nm to 200 nm.

[0234] The method for forming the transparent electrode used in the present invention is not particularly limited as long as it is a method that can form a transparent electrode with a desired thickness. As a method for forming such a transparent electrode, a general electrode film formation method can be used, for example, a PVD method such as a vacuum deposition method, a sputtering method, an ion plating method, a CVD method, a method of applying a conductive paste, etc. are included. In addition, the transparent electrode may be formed on the entire surface of the underlying layer or the surface of the transparent electrode substrate, or may be formed in a pattern on the underlying layer or the surface of the transparent electrode substrate.

[0235] The transparent electrode used in the present invention may be disposed independently, or may be formed on a transparent electrode substrate. In this case, as described above, the electrode portion is disposed so as to face the display medium layer 110.

[0236] [Display media layer] The display medium layer 110 used in the present invention is appropriately selected depending on the display method of the electronic paper. The display method of the electronic paper can be a known one, such as an electrophoretic method, a twist ball method, a powder migration method (electronic liquid powder method, charged toner type method), a liquid crystal display method, a thermal method (coloring method, light scattering method), an electrochromic method, an electrowetting method, a magnetophoretic method, etc. In the present invention, the electrophoretic method is preferably used. This is because this method has entered the practical stage and, being a particle migration type, it is possible to obtain electronic paper that has little viewing angle dependency and excellent responsiveness.

[0237] The electrophoretic method utilizes the electrophoretic phenomenon in which charged particles dispersed in a solvent move between electrodes due to an electric field. Examples of the electrophoretic method include a microcapsule method and a microcup method.

[0238] In the microcapsule method, charged white and black particles (display media 112, 113) and a transparent dispersion medium 111 that disperses these particles are encapsulated in a microcapsule made of transparent resin, and black and white display or gradation is expressed by moving the white and black particles up and down by applying an electric field. In the microcup method, a dye-colored dispersion medium and charged white particles are placed in a cell partitioned by a cup-shaped depression (microcup), and white or the color of the dispersion medium is displayed by moving the white particles up and down by applying an electric field.

[0239] The structure, material and method of formation of the display medium layer used in the present invention may be the same as those used in general electronic paper for each display method.

[0240] The following description will be given taking the display medium layer in the case of the microcapsule method as an example. For example, such a display medium layer may be one in which microcapsules containing a dispersion liquid consisting of white particles, black particles (display media 112, 113) and a transparent dispersion medium 111 are fixed with a binder resin.

[0241] As the transparent dispersion medium 111, for example, alcohol solvents, various esters, ketones, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, halogenated hydrocarbons, carboxylates, or various other oils, etc., can be used alone or in combination with a surfactant or the like.

[0242] As the white particles, for example, white pigments such as titanium dioxide, zinc oxide, antimony trioxide, etc. can be used, and as the black particles, for example, black pigments such as aniline black, carbon black, titanium black, etc. Furthermore, if necessary, to these pigments, a charge control agent consisting of particles such as electrolytes, surfactants, metal soaps, resins, rubbers, oils, varnishes, compounds, etc., a dispersant such as a titanium-based coupling agent, an aluminum-based coupling agent, a silane-based coupling agent, etc., a lubricant, a stabilizer, etc. may be added.

[0243] Examples of materials that can be used to form the wall of a microcapsule include a composite membrane of gum arabic and gelatin, and compounds such as urethane resin, urea resin, and urea resin.

[0244] As the binder resin, a resin that has good affinity with the wall film of the microcapsule, excellent adhesion to the transparent electrode, and insulating properties can be used, such as polyethylene, chlorinated polyethylene, ethylene-vinyl acetate copolymer, silicone resin, etc.

[0245] Such a display medium layer can be formed, for example, by dispersing microcapsules in a binder resin to form an ink, which is then applied onto the transparent electrode.

[0246] [Back electrode] The rear electrode 180 used in the present invention has a rear electrode substrate and a rear electrode layer formed on the rear electrode substrate. In this case, as described above, the electrode portion is disposed so as to face the display medium layer 110.

[0247] (back electrode layer) The back electrode layer used in the present invention may be a pixel electrode layer formed perpendicular to the stripe pattern of the back electrode layer, or may be a TFT electrode layer having a plurality of TFT elements and pixel electrodes connected to the TFT elements. By using the former, a passive matrix type electronic paper can be obtained, and by using the latter, an active matrix type electronic paper can be obtained. Among them, in the present invention, it is preferable to use the TFT electrode layer. An active matrix type electronic paper with high contrast and fast response speed can be obtained.

[0248] Fig. 10 is a cross-sectional view showing another example of a reflective display device according to an embodiment of the present invention. This embodiment differs from Fig. 9 in that a second laminate 100C is laminated instead of the first laminate 100A. According to this embodiment, for example, glass is used as the support 150, and an anti-reflection layer and / or an anti-glare layer 160 can be formed on the surface of this glass via an adhesive layer 140.

[0249] FIG. 11 is a cross-sectional view showing still another example of a reflective display device according to an embodiment of the present invention. 10 in that a second laminate 100D is laminated instead of the second laminate 100C. As in this embodiment, in the present invention, the substrate 120 may be laminated via the adhesive layer 140.

[0250] In the reflective display device of the present invention, a front panel may be formed by a laminate exemplified by first laminate 100A, 100B, second laminate 100C, 100D, and transparent electrode 170, and a rear panel may be formed by rear electrode 180, and the front panel, display medium layer 110, and rear panel may be laminated in that order.

[0251] As described above, the reflective display device of the present invention has first laminates 100A, 100B and second laminates 100C, 100D arranged on the transparent electrode 170 side, thereby exhibiting high barrier performance against gas and moisture, and thus making it possible to prevent external gas and moisture from penetrating from the transparent electrode 170 side. This makes it possible to prevent deterioration of the display medium layer and the like due to contact with gas and moisture, and improve the durability of the electronic paper. EXAMPLES

[0252] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these descriptions. First, barrier films according to Example 1 and Comparative Examples 1 to 4 were produced using the film-forming apparatus and film-forming method described in this embodiment. Pretreatment conditions, deposition conditions, etc. are summarized in Table 1. In the following tables, "o" in the evaluation of "with or without plasma pretreatment" means that plasma pretreatment was performed, and "x" means that plasma pretreatment was not performed. In addition, in the evaluation of "with or without plasma assistance during deposition", "o" means that plasma assistance was performed during deposition, and "x" means that plasma assistance was not performed during deposition.

[0253] Comparative Example 1 A biaxially oriented polyethylene terephthalate film (PET film) having a thickness of 12 μm was used as the substrate 120, and a plasma pretreatment step and a film formation step were carried out using the film formation apparatus 10 shown in FIG.

[0254] In the pretreatment step, the surface of the substrate 120 was subjected to plasma pretreatment using the plasma pretreatment mechanism 11B shown in Figs. 4 and 5. Specifically, first, a mixed gas of oxygen (O2):argon (Ar) (O2:Ar = 2.5:1) was supplied to the plasma pretreatment chamber 12B using the plasma raw material gas supply unit, while the pressure inside the plasma pretreatment chamber 12B was adjusted using the reduced pressure chamber 12. Next, a voltage was applied between the pretreatment roller 20 and the electrode unit 21 to generate plasma, and the surface of the substrate 120 was subjected to plasma pretreatment. The pressure inside the plasma pretreatment chamber 12B was 6.2 Pa, and a 1000 Gauss permanent magnet was used as the magnetic field generating unit 23. The plasma density was 417 W·sec / m 2 It was.

[0255] In the film formation process, an evaporation mechanism 24 as shown in FIG. 8 is used to evaporate an acid by vacuum deposition. Specifically, the degree of vacuum in the film formation chamber 12C was adjusted to 1.5 Pa, and then, while aluminum metal wires were supplied as a deposition material into the boat 24b, the deposition material in the boat 24b was heated using the resistance heating evaporation mechanism 24, and the aluminum was evaporated so as to reach the surface of the base material 120. At the same time, while oxygen was supplied at 12500 sccm, the deposition film 130b was formed on the surface of the base material 120.

[0256] In addition, the plasma supply mechanism 50 used had a hollow cathode 51 as shown in FIG. 8 and an anode (not shown) arranged on both sides of the substrate 120 in the width direction as viewed from the boat 24b, facing the opening of the hollow cathode 51. A plasma raw material gas (O2:Ar=35:1) was supplied to the hollow cathode 51 and discharged to excite plasma. This plasma was then extracted by the opposing anode to between the surface of the substrate 120 and the evaporation mechanism 24, thereby providing plasma assistance during deposition.

[0257] By the above method, the deposited film 130b was laminated on the substrate 120. The conveying speed at this time was 300 m / min, and the deposited film 130b had a thickness of 25 nm.

[0258] Example 1 The barrier film of Example 1 was produced in the same manner as in Comparative Example 1, except that the following organic coating layer 130a was laminated on the vapor-deposited film 130b of Comparative Example 1.

[0259] 307g of water, 147g of isopropyl alcohol, and 7.3g of 0.5N hydrochloric acid were mixed, and the solution was adjusted to pH 2.2. Then, 175g of tetraethoxysilane as a metal alkoxide and 8.7g of glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed while cooling to 10°C to prepare solution A. 14.7g of polyvinyl alcohol having a polymerization degree of 2400 and a saponification value of 99% or more, 324g of water, and 17g of isopropyl alcohol were mixed as a hydroxyl group-containing water-soluble resin to prepare solution B. The solution obtained by mixing solution A and solution B at a mass ratio of 6.5:3.5 was used as a barrier coating agent. The barrier coating agent prepared above was coated on the aluminum oxide vapor deposition film of the PET film by spin coating. Then, the mixture was heated in an oven at 180°C for 60 seconds to form an organic coating layer with barrier properties of about 400 nm on the aluminum oxide vapor deposition film, and the barrier film of Example 1 was produced.

[0260] Example 2 In Example 1, the process of laminating the vapor-deposited film 130b and the organic coating layer 130a was further repeated under the same conditions as in Example 1, and a barrier film having a four-layer structure of the barrier layer, i.e., substrate / vapor-deposited film 130b / organic coating layer 130a / vapor-deposited film 131b / organic coating layer 131a, was produced as Example 2.

[0261] (Reference example 1) A barrier film of Reference Example 1 was produced in the same manner as in Example 1, except that the conveying speed was 150 m / min and the thickness of the deposited film 130b was 50 nm.

[0262] (Reference example 2) In Reference Example 1, the process of laminating the vapor-deposited film 130b and the organic coating layer 130a was further repeated under the same conditions as in Reference Example 1, and a barrier film having a four-layer barrier layer structure of substrate / vapor-deposited film 130b / organic coating layer 130a / vapor-deposited film 131b / organic coating layer 131a was produced as Reference Example 2.

[0263] Comparative Example 2 A barrier film of Comparative Example 2 was produced in the same manner as in Example 1, except that the conveying speed was 600 m / min and the thickness of the vapor-deposited film 130b was 8 nm.

[0264] Comparative Example 3 A barrier film of Comparative Example 3 was produced in the same manner as in Example 1, except that the conveying speed was 480 m / min and the thickness of the deposited film 130b was 13 nm.

[0265] Comparative Example 4 The barrier film of Comparative Example 4 was produced in the same manner as in Comparative Example 1, except that the conveying speed was 480 m / min, the oxygen supply amount during deposition was 6000 sccm, the thickness of the deposited film 130b was 10 nm, and plasma assistance was not performed during deposition.

[0266] [Table 1]

[0267] [TOF-SIMS analysis] For the barrier films of the examples and comparative examples, mass analysis was performed using a time-of-flight secondary ion mass spectrometer (TOF.SIMS5, manufactured by ION TOF) under the following measurement conditions from the surface side of the vapor deposition film of the barrier film, while repeatedly soft etching at a constant rate with a Cs (cesium) ion gun. The following mass analysis results were obtained: C6 (mass number 72.00) derived from the resin substrate, Al2O3 (mass number 101.94) derived from the aluminum oxide vapor deposition film, Al2O4H (mass number 118.93) derived from the aluminum oxide vapor deposition film, Al3 (mass number 80.94) derived from the aluminum oxide vapor deposition film, and Si (mass number 27.97) derived from the organic coating layer as required. Graphical analysis diagrams of the measurement results are shown in Figures 12 to 16. Figure 12 shows the measurement results of Comparative Example 1, Figure 13 shows the measurement results of Example 1, Figure 14 shows the measurement results of Comparative Example 2, Figure 15 shows the measurement results of Comparative Example 3, and Figure 16 shows the measurement results of Comparative Example 4. In the figure, the unit of the vertical axis (intensity) is the common logarithm of the ion intensity, and the unit of the horizontal axis (Et times (s)) is the number of seconds during which etching was performed.

[0268] TOF-SIMS measurement conditions Primary ion type: Bi 3++ (0.2pA, 100μs) ·Measurement area: 150×150μm 2 Etching gun type: Cs (1keV, 60nA) Etching area: 600×600μm 2 Etching rate: 10sec / cycle

[0269] In addition, the position showing the measured intensity peak of the element bond Al2O4H was determined in terms of the number of etching seconds (peak position Y), and the depth position of that position from the surface of the primer layer side of the evaporated film (peak position Y / X in the drawing, unit %) was determined. These results are summarized in Table 2.

[0270] [Table 2]

[0271] (Barrier property evaluation) The water vapor permeability and oxygen permeability of each of the barrier films of the Examples, Comparative Examples, and Reference Examples produced by the above-mentioned methods were measured.

[0272] The water vapor transmission rate was measured using a water vapor transmission rate measuring device (manufactured by Mocon, product name "Permatran") at 40°C and 100% RH in accordance with JIS K 7129 B. The oxygen transmission rate was measured using an oxygen transmission rate measuring device (manufactured by Mocon, product name "OXTRAN") at 23°C and 90% RH in accordance with JIS K 7126-2. The results are shown in Table 3.

[0273] (Optical properties) Color difference (L * a * b * The color space was measured using a spectrophotometer CM-700d in accordance with JIS Z8722. The barrier film was placed on a white board and the measurements were performed. The results are shown in Table 3.

[0274] [Table 3]

[0275] From Tables 2 and 3, it can be seen that Example 1, in which the intensity derived from elemental bond Al2O4H is present at a depth position of 50% to 99% from the film interface on the side opposite to the substrate of the vapor-deposited film, the intensity ratio (Al2O4H / Al2O3) detected at the position of the maximum peak is 1.0 or more, and no intensity peak derived from elemental bond Al3 is detected, has higher barrier properties than Comparative Examples 2 and 3. Therefore, it can be seen that the laminates using the barrier films of the examples have high barrier properties.

[0276] In Comparative Example 4, an intensity peak derived from elemental bond Al3 is detected due to the small amount of oxygen supplied during deposition. And, it can be seen from the evaluation of optical properties that although the barrier property is high, the transparency is poor.

[0277] The water vapor barrier properties of Examples 1 and 2 and Reference Examples 1 and 2 were 0.1 g / m 2 ·day or less, and in particular, the water vapor barrier property of Reference Example 2 is 0.01 g / m 2 · Less than 10 days -3 Both values ​​are suitable for use in electronic paper. [Explanation of symbols]

[0278] 10 Film deposition equipment P Plasma X Rotation Axis 11A Substrate transport mechanism 11B Plasma pretreatment mechanism 11C Film formation mechanism 12 Decompression chamber 12A Substrate transport chamber 12B Plasma pretreatment chamber 12C Deposition chamber 13 Unwinding roller 14a~d Guide roll 15 Winding roller 20 Pre-treatment roller 21 Electrode part 23 Magnetic field forming part 23a 1st page 23b 2nd side 231 First Magnet 231c 1st axis direction part 232 Second Magnet 232c 2nd axis direction part 232d Connection part 24 Evaporation mechanism 24b Boat 25 Coating roller 31 Power supply wiring 32 Power supply 35a~35c Bulkhead 50 Plasma supply mechanism 51 Hollow Cathode 61 Vapor deposition material supply section 63 Aluminum Vapor 100A, 100B First laminate 100C, 100D Second laminate 110 Display media layer 111 Dispersion medium 112, 113 Display media 1, 120 base material 130, 135 Barrier layer 130a, 131a Organic coating layer 130b, 131b Aluminum oxide vapor deposition film 140 Adhesive layer or adhesive layer 150 Support 160 Anti-reflection and / or anti-glare layer 161 Resin 162 particles 170 Transparent electrode (ITO) 180 Back electrode (TFT) 200A, 200C, 200D reflective display

Claims

1. a barrier film including at least a substrate, an aluminum oxide vapor deposition film, and an organic coating layer laminated in this order; A laminate comprising a support and an antireflection layer and / or an antiglare layer formed on a surface of the support opposite to the barrier film, an adhesive layer is disposed between the barrier film and the support; When the barrier film was etched from the surface side opposite the substrate by time-of-flight secondary ion mass spectrometry (TOF-SIMS), The aluminum oxide vapor deposition film region contains elemental bond Al 2 O 3 Strength derived from elemental bond Al 2 O 4 Intensity from H and The element bond Al 2 O 4 an intensity derived from H has a maximum peak, the maximum peak being present at a depth position of 50% to 99% from a film interface on a side of the aluminum oxide vapor-deposited film opposite to the substrate; The element bond Al detected at the position of the maximum peak 2 O 3 The element bond Al to 2 O 4 H intensity ratio (Al 2 O 4 H / Al 2 O 3 ) is 1.0 or more, The aluminum oxide vapor deposition film region contains elemental bond Al 3 No intensity peaks were detected. The thickness of the aluminum oxide vapor deposition film is 25 nm or more and 50 nm or less, A laminate for a reflective display device, wherein the barrier film is formed by stacking at least a substrate, a first aluminum oxide vapor deposition film, a first organic coating layer, a second aluminum oxide vapor deposition film, and a second organic coating layer in this order.

2. The laminate according to claim 1 , wherein the aluminum oxide vapor-deposited film has a thickness of more than 15 nm and less than 60 nm.

3. 3. The laminate according to claim 1, wherein the organic coating layer is a cured product of a resin composition containing a metal alkoxide and a hydroxyl group-containing water-soluble resin.

4. A reflective display device comprising: two opposing electrodes, at least one of which is a transparent electrode; and a display medium layer disposed between the electrodes and including a display medium, The laminate according to claim 1 is provided on the transparent electrode side, A reflective display device, wherein the anti-reflection layer and / or the anti-glare layer is disposed on the outer side.

5. A front panel is formed by the laminate according to any one of claims 1 to 3 and the transparent electrode, 5. The reflective display device according to claim 4, wherein the front plate, the display medium layer, and a rear plate including a rear electrode are laminated in this order.

Citation Information

Patent Citations

  • Antiglare gas barrier film and method for producing the same

    JP2011240668A

  • Gas barrier film and manufacturing method of gas barrier film

    JP2016203427A

  • Electronic paper

    JP2019060946A

  • Barrier film, laminate using said barrier film, packaging product using said laminate

    WO2021045127A1